Effects of Lactobacillus- and Bacillus-based probiotics on growth performance, intestinal barrier function, and microbiota modulation in nursery pigs: A meta-analysis - K. Sahatsanon; A. Jayanegara; S.W. Kim; Y. Ruangpanit; C.-S. Lin; P. Sivapirunthep; C. Chaosap (Animal Feed Science and Technology, 2026)

Storage timescales and the crystal growth history recorded in the layered reservoir of the Unit 3 Kulanaokuaiki Tephra Member of the Uēkahuna Ash from Kīlauea volcano - Abigail R. Nalesnik; Kendra J. Lynn; Timothy R. Rose; Jessica M. Warren; Dawn C. S. Ruth; Kuan-Yu Lin; Donald A. Swanson (Contributions to Mineralogy and Petrology, 2026)
The Kulanaokuaiki Tephra Unit 3 (900 C.E.) was a subplinian basaltic scoria eruption, the largest known to have occurred at Kīlauea’s summit. The initiation mechanism and cause(s) of this highly hazardous eruption remain poorly understood, particularly as this style of activity has not been observed in the modern period. We use olivine diffusion timescales from Fe-Mg and lithium zoning to assess magma storage timescales and evaluate evidence for mixing prior to eruption. Of the 200 crystals assessed, 55% are normally zoned for forsterite and 45% are non-zoned. Zoned crystals (> 1 mm) ( n = 96) have average compositions of Fo 89 cores and Fo 81 rims, while small crystals 0.5–1 mm ( n = 14) have Fo 85 cores and Fo 82 rims. Modeled Fo diffusion timescales range from n = 17), reflecting growth processes and precluding their use for diffusion studies. Overall, our Unit 3 olivine dataset displays no evidence of magmatic priming shortly prior to eruption, unlike prior observations for the basaltic subplinian eruption of the Keanakāko‘i Tephra Unit E (1650 C.E.). Thus, explosive eruption magmas may be stored for considerably longer than previously thought, and magmatic priming is not a necessary precursor for Kīlauea’s explosive eruptions. We hypothesize that gas-driven filter pressing from crystallization of microlites and macrocrysts in the reservoir slurry contributed to the explosivity of the Unit 3 eruption.

Magmatic evolution characteristics and heterogeneity of the outer zone of the Emeishan Large Igneous Province: a case study of basalts from the Tianquan and Huayingshan areas - C. C. Li; S. Yang; Z. Y. Lin; Y. P. Jing; Y. Xia; Y. H. Chen; J. T. Liao; C. D. Nie (Australian Journal of Earth Sciences, 2026)

Dietary Patterns Associated With Weight Loss Among Patients With Colorectal Cancer During the First 6 Months After Diagnosis: A Cross-Sectional Analysis From the ColoCare Study - Rachel Hoobler; Fred K. Tabung; Tengda Lin; Biljana Gigic; Kristen S. Smith; Kary Woodruff; Sylvia L. Crowder; Sheetal Hardikar; Doratha A. Byrd; Adriana M. Coletta; Alejandro Sanchez; Amandine Chaix; et al. (Journal of the Academy of Nutrition and Dietetics, 2026)

A comprehensive review of phage immobilization and encapsulation for the application in food safety - Pankaj Koirala; Yen-Te Liao; Meng-Wei Lin; Shyam S. Sablani; Vivian C. H. Wu (Critical Reviews in Food Science and Nutrition, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

The learning efficiency of the ant Anoplolepis gracilipes (Hymenoptera: Formicidae) varies with temperature - C.-H. Chan; T.-S. Lin; H.-D. Lin; C.-I. Chiu (Insectes Sociaux, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

An in vitro-in silico workflow for predicting renal clearance of environmental chemicals and drugs - Courtney Sakolish; Hsing-Chieh Lin; Haley L. Moyer; Lucie C. Ford; Charles H. Christen; Barbara A. Wetmore; Michael J. DeVito; Philip Hewitt; Stephen S. Ferguson; Farah Raad; Ivan Rusyn; Weihsueh A. Chiu (Toxicology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Fetal response to maternal exposures of environmental chemicals: Utility of a four-cell human feto-maternal interface organ-on-chip - Haley L. Moyer; SungJin Kim; Bowie P. Lam; Lauren S. Richardson; Han-Hsuan D. Tsai; Lucie C. Ford; Hsing-Chieh C. Lin; Weihsueh A. Chiu; Ramkumar Menon; Arum Han; Ivan Rusyn (Chemico-Biological Interactions, 2025)

P20-17 Polyethylene terephthalate (PET) nanoplastics induce acute pulmonary inflammation in mice - Ø.P. Haugen; L.M.A. Camassa; H.F. Berntsen; F.-C. Lin; V. Alcolea-Rodriguez; R. Portela; F. Barbero; O.A.H. Foss; H. Sadeghiankaffash; Ø. Skare; S. Alsaedi; A.L. Moen; et al. (Toxicology Letters, 2025)

Diaporthe manilkarae sp. nov. ( Diaporthaceae ) on Manilkara zapota (Sapotaceae) from Guangdong Province, China - Yanhong Lin; Indunil C. Senanayake; Ishara S. Manawasinghe; Yunxia Zhang (New Zealand Journal of Botany, 2025)
Manilkara zapota (L.) P. Royen is an evergreen ornamental and fruit tree distributed in tropical and subtropical regions. In 2022, a leaf spot disease was observed on M . zapota plants in Guangdong Province, China. The putative pathogen was isolated and identified based on morphology and multi‐locus phylogenetic analyses of tub2 , ITS, tef1‐α , cal and his3 . Based on morphology and phylogenetic analyses, the causal agent was identified as a novel species namely Diaporthe manilkarae . Furthermore, pathogenicity essays were conducted using potted seedlings to confirm the pathogenicity. The results revealed that this fungus was able to infect wounded M. zapota leaves and develop typical symptoms similar to field symptoms whereas control and non‐wounded leaves remained asymptomatic. This study will contribute to the knowledge of fungi associated with M. zapota . Further studies are required to understand the pathogenicity of this fungi on other fruit crops.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Relational characteristics and dynamics between high-tech firms in the Pearl River Delta and the empowerment for technological innovation by Hong Kong - Jili Xu; Anthony G. O. Yeh; George C. S. Lin; Xingjian Liu; Fan Fiona Yang; Zixin Luo (Journal of Geographical Sciences, 2025)

A web-based histology atlas for the freshwater sentinel species Daphnia magna - Mee S. Ngu; Daniel J. Vanselow; Carolyn R. Zaino; Alex Y. Lin; Jean E. Copper; Margaret J. Beaton; Luisa Orsini; John K. Colbourne; Keith C. Cheng; Khai C. Ang (Science of The Total Environment, 2025)

Development and use of DJ-1 affinity microcolumns to screen and study small drug candidates for Parkinson's disease - Jacob C. Jones; Jiusheng Lin; Sadia Sharmeen; Md Masudur Rahman; Ha H. Truong; Ting-Rong Chern; Mark A. Wilson; David S. Hage (Analytica Chimica Acta, 2025)

Fluid inclusion characteristics and mechanisms of tin mineralisation in the Jialong tin polymetallic deposits, Jiuwandashan–Yuanbaoshan, northern Guangxi, China - C-L. Meng; L-A. Bai; Z-H. Yue; S-Y. Zhou; Y. Dai; Z-H. Feng; X-J. Liu; H. Zhang; L-Z. Lin (Australian Journal of Earth Sciences, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Identification of pollution sources in rivers by downstream analysis of low-concentration elements associated with wastewater - H.-C. Lin; P.-Y. Hsieh; G.-S. Wang; D.-W. Wang; T.-H. Wang; Y.-C. Hsu; C.-F. Wu (International Journal of Environmental Science and Technology, 2024)

Enhanced removal of rare earth elements from aqueous media: exploring the potential of AM-3 and AM-4 titanosilicates - Joana C. Almeida; Cátia Sousa; Daniela S. Tavares; João Pinto; Bruno Henriques; Zhi Lin; João Rocha; Eduarda Pereira (Environmental Science and Pollution Research, 2024)
This study investigates the impact of three key variables on the performance of nanoporous AM-3 and layered AM-4 titanosilicates in removing nine REEs (Y, La, Ce, Pr, Nd, Eu, Gd, Tb, and Dy) from natural mineral water and identifies optimal operational conditions using Response Surface Methodology (RSM). The experimental conditions were determined by a Box-Behnken Design of 3 factors-3 levels (pH 4, 6, and 8; sorbent dose 20, 100, and 180 mg/L; and element concentration 1, 3, and 5 μmol/L). Three-dimensional response surfaces were used to assess the linear, quadratic, and interaction influences of each factor on the REEs’ removal percentage. The pH was the most significant factor in the removal process using AM-3, while the sorbent dose was more important for AM-4. The results highlighted the sorbents’ strong capacity for REE removal. The optimal operating conditions obtained by RSM were applied to aqueous solutions with salinity 10 (common in coastal and transitional systems) and 30 (average seawater salinity). The results showed that AM-3 has a strong potential for removing REEs in solutions with salinity 10 and 30, while AM-4 was less efficient due to competition between REEs and other ions present in the solution.

FDA-approved disulfiram as a novel treatment for aggressive leukemia - Mawar Karsa; Lin Xiao; Emma Ronca; Angelika Bongers; Dayna Spurling; Ayu Karsa; Sandra Cantilena; Anna Mariana; Tim W. Failes; Greg M. Arndt; Laurence C. Cheung; Rishi S. Kotecha; et al. (Journal of Molecular Medicine, 2024)
Acute leukemia continues to be a major cause of death from disease worldwide and current chemotherapeutic agents are associated with significant morbidity in survivors. While better and safer treatments for acute leukemia are urgently needed, standard drug development pipelines are lengthy and drug repurposing therefore provides a promising approach. Our previous evaluation of FDA-approved drugs for their antileukemic activity identified disulfiram, used for the treatment of alcoholism, as a candidate hit compound. This study assessed the biological effects of disulfiram on leukemia cells and evaluated its potential as a treatment strategy. We found that disulfiram inhibits the viability of a diverse panel of acute lymphoblastic and myeloid leukemia cell lines ( n = 16) and patient-derived xenograft cells from patients with poor outcome and treatment-resistant disease ( n = 15). The drug induced oxidative stress and apoptosis in leukemia cells within hours of treatment and was able to potentiate the effects of daunorubicin, etoposide, topotecan, cytarabine, and mitoxantrone chemotherapy. Upon combining disulfiram with auranofin, a drug approved for the treatment of rheumatoid arthritis that was previously shown to exert antileukemic effects, strong and consistent synergy was observed across a diverse panel of acute leukemia cell lines, the mechanism of which was based on enhanced ROS induction. Acute leukemia cells were more sensitive to the cytotoxic activity of disulfiram than solid cancer cell lines and non-malignant cells. While disulfiram is currently under investigation in clinical trials for solid cancers, this study provides evidence for the potential of disulfiram for acute leukemia treatment. Key messages Disulfiram induces rapid apoptosis in leukemia cells by boosting oxidative stress. Disulfiram inhibits leukemia cell growth more potently than solid cancer cell growth. Disulfiram can enhance the antileukemic efficacy of chemotherapies. Disulfiram strongly synergises with auranofin in killing acute leukemia cells by ROS induction. We propose testing of disulfiram in clinical trial for patients with acute leukemia.

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

Did Early Pleistocene hominins control hammer strike angles when making stone tools? - Li Li; Jonathan S. Reeves; Sam C. Lin; David R. Braun; Shannon P. McPherron (Journal of Human Evolution, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Geological controls on the distribution of gas hydrates in the shallow parts of the gas hydrate stability zone – constraints from seafloor drilling off Taiwan - G. Bohrmann; C. Berndt; S. Lin; T.-H. Tu; A.T. Lin; H.-H. Hsu; M.-C. Lai; W.-C. Chi; C. Deusner; J. Elger; K. Wallmann; T. Freudenthal; et al. (Marine and Petroleum Geology, 2023)

Cost-effective and accurate monitoring of flowering across multiple tropical tree species over two years with a time series of high-resolution drone imagery and deep learning - Calvin Ka Fai Lee; Guangqin Song; Helene C. Muller-Landau; Shengbiao Wu; S. Joseph Wright; K.C. Cushman; Raquel Fernandes Araujo; Stephanie Bohlman; Yingyi Zhao; Ziyu Lin; Zounachuan Sun; Peter Chuen Yan Cheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Efficient adsorption and photocatalytic degradation of water emerging contaminants through nanoarchitectonics of pore sizes and optical properties of zirconium-based MOFs - Jia-Xuan Tan; Zih-Yu Chen; Celine H. Chen; Ming-Feng Hsieh; Angela Yu-Chen Lin; Season S. Chen; Kevin C.-W. Wu (Journal of Hazardous Materials, 2023)

A Letter to Your Care Providers: Implementation and Analysis of a Letter-based Advance Care Planning Initiative for Gynecologic Oncology Patients - Catherine N. Zivanov; Anne Coogan; Robin R. Lane; Sara G. Lin; Sarah C. Reed; Marc A. Robinson; Mohana Karlekar; Lauren S. Prescott; Alaina J. Brown (Journal of Cancer Education, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Whole bone subcutaneous transplantation as a strategy to study precisely the bone marrow niche - Caroline C. Picoli; Patrícia Rocha Martins; Xiao Lin Casey Wong; Thamires Righi; Pedro P. G. Guimarães; Mauro C. X. Pinto; Jaime H. Amorim; Vasco A. C. Azevedo; Silma Regina Pereira; Alexandre Kanashiro; Fabio Cardoso Cruz; Rodrigo R. Resende; et al. (Stem Cell Reviews and Reports, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Recent Developments in Additive-Manufactured Intermetallic Compounds for Bio-Implant Applications - Po-Yuan Yeh; Jacob C. Huang; Jason S. C. Jang; Cheng-Tang Pan; Chung-Hwan Chen; Che-Hsin Lin (Journal of Medical and Biological Engineering, 2022)
Purpose This paper reviews the recent developments of two newly developed intermetallic compounds (IMCs) of metallic glasses (MGs) and high-entropy alloys (HEAs) as potential implantable biomaterials. Methods The paper commences by summarizing the fundamental properties of recently developed MGs and high-entropy alloys (HEAs). A systematic review is presented of the recent literature about the use of AM technology in fabricating MG and HEA components for biological implant applications. Results The high strength, low Young’s modulus, and excellent corrosion resistance make these IMCs good candidates as bio-implantable materials. Recent studies have shown that additive manufacturing (AM) techniques provide an advantageous route for the preparation of glassy metallic components due to their intrinsically rapid cooling rates and ability to fabricate parts with virtually no size or complexity constraints. A practical example is conducted by AM producing a porous gradient Ti-based MG spinal cage. The produced MG powders and the in vivo test results on an 18 M-old Lanyu pig confirm the feasibility of the AM technique for producing implantable IMC-based prosthesis. Conclusion The non-crystalline structure of MGs alloy and the random crystalline composition of HEAs provide unique material properties that will substantially impact the development of future implantable prostheses.

BCL11B Upregulates the Expression of RelA in T Cells Stimulated with Staphylococcal Enterotoxin A - Y. Yan; S. Wang; C. Lin (Bulletin of Experimental Biology and Medicine, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Quantifying knapping actions: a method for measuring the angle of blow on flakes - Li Li; Jonathan S. Reeves; Sam C. Lin; Claudio Tennie; Shannon P. McPherron (Archaeological and Anthropological Sciences, 2022)
Stone artifacts are critical for investigating the evolution of hominin behavior—they are among our only proxies for hominin behavior in deep time. Hominin cognition and skill are often inferred by reconstructing the technical decisions hominins made throughout the knapping process. However, despite many advancements in understanding how hominins knapped, some of the key factors involved in past flake production cannot be easily/readily derived from stone artifacts. In particular, the angle at which the knapper strikes the hammer against the core to remove the flake, or the angle of blow, is a key component of the knapping process that has up to now remained unmeasurable on archeological assemblages. In this study, we introduce a new method for estimating the angle of blow from the ventral surface of flakes. This method was derived from a controlled experiment that explicitly connects fracture mechanics to flake variability. We find that a feature of the flake’s bulb of percussion, what we call the bulb angle, is a measurable indicator of the angle of blow. Our experimental finding is further validated in two additional datasets from controlled and replicative knapping experiments. These results demonstrate the utility of continuing to link flake variation with technical decision-making to fracture mechanics. In addition, they also provide a useful and relatively simple means to capture a currently invisible aspect of hominin stone tool production behavior.

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

P75 neurotrophin receptor controls subventricular zone neural stem cell migration after stroke - Sachin S. Deshpande; Subash C. Malik; Pasquale Conforti; Jia-di Lin; Yu-Hsuan Chu; Suvra Nath; Franziska Greulich; Meike-Ast Dumbach; N. Henriette Uhlenhaut; Christian Schachtrup (Cell and Tissue Research, 2022)
Stroke is the leading cause of adult disability. Endogenous neural stem/progenitor cells (NSPCs) originating from the subventricular zone (SVZ) contribute to the brain repair process. However, molecular mechanisms underlying CNS disease-induced SVZ NSPC-redirected migration to the lesion area are poorly understood. Here, we show that genetic depletion of the p75 neurotrophin receptor ( p75 NTR−/− ) in mice reduced SVZ NSPC migration towards the lesion area after cortical injury and that p75 NTR−/− NSPCs failed to migrate upon BDNF stimulation in vitro. Cortical injury rapidly increased p75 NTR abundance in SVZ NSPCs via bone morphogenetic protein (BMP) receptor signaling. SVZ-derived p75 NTR−/− NSPCs revealed an altered cytoskeletal network- and small GTPase family-related gene and protein expression. In accordance, BMP-treated non-migrating p75 NTR−/− NSPCs revealed an altered morphology and α-tubulin expression compared to BMP-treated migrating wild-type NSPCs. We propose that BMP-induced p75 NTR abundance in NSPCs is a regulator of SVZ NSPC migration to the lesion area via regulation of the cytoskeleton following cortical injury.

A bibliometric review of peripartum cardiomyopathy compared to other cardiomyopathies using artificial intelligence and machine learning - M. Grosser; H. Lin; M. Wu; Y. Zhang; S. Tipper; D. Venter; J. Lu; C. G. dos Remedios (Biophysical Reviews, 2022)

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Effect of water regime and harvest stage on essential oil accumulation in basil plant growing in sandy soil - João V. R. S. Souza; Lin Chau Ming; Marcos A. L. Santos; James E. Simon; Hector R. Juliani; João C. C. Saad (Irrigation Science, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

The influence of vector‐borne disease on human history: socio‐ecological mechanisms - Tejas S. Athni; Marta S. Shocket; Lisa I. Couper; Nicole Nova; Iain R. Caldwell; Jamie M. Caldwell; Jasmine N. Childress; Marissa L. Childs; Giulio A. De Leo; Devin G. Kirk; Andrew J. MacDonald; Kathryn Olivarius; et al. (Ecology Letters, 2021)
Vector‐borne diseases (VBDs) are embedded within complex socio‐ecological systems. While research has traditionally focused on the direct effects of VBDs on human morbidity and mortality, it is increasingly clear that their impacts are much more pervasive. VBDs are dynamically linked to feedbacks between environmental conditions, vector ecology, disease burden, and societal responses that drive transmission. As a result, VBDs have had profound influence on human history. Mechanisms include: (1) killing or debilitating large numbers of people, with demographic and population‐level impacts; (2) differentially affecting populations based on prior history of disease exposure, immunity, and resistance; (3) being weaponised to promote or justify hierarchies of power, colonialism, racism, classism and sexism; (4) catalysing changes in ideas, institutions, infrastructure, technologies and social practices in efforts to control disease outbreaks; and (5) changing human relationships with the land and environment. We use historical and archaeological evidence interpreted through an ecological lens to illustrate how VBDs have shaped society and culture, focusing on case studies from four pertinent VBDs: plague, malaria, yellow fever and trypanosomiasis. By comparing across diseases, time periods and geographies, we highlight the enormous scope and variety of mechanisms by which VBDs have influenced human history.

Atrial fibrillation rhythm is associated with marked changes in metabolic and myofibrillar protein expression in left atrial appendage - Julie H. Rennison; Ling Li; Cheryl R. Lin; Beth S. Lovano; Laurie Castel; Sojin Youn Wass; Catherine C. Cantlay; Meghan McHale; A. Marc Gillinov; Reena Mehra; Belinda B. Willard; Jonathan D. Smith; et al. (Pflügers Archiv - European Journal of Physiology, 2021)

Characterization and validation of QTLs for adult plant stripe rust resistance in Chinese wheat landrace Dabaimai - M. Y. Wang; M. R. Xu; F. T. Wang; S. J. A. Shah; J. Feng; R. M. Lin; S. C. Xu (Cereal Research Communications, 2021)

Fracture Propagation of Rock like Material with a Fluid-Infiltrated Pre-existing Flaw Under Uniaxial Compression - C. Wei; B. Zhang; W. Zhu; S. Wang; J. Li; ·L. Yang; C. Lin (Rock Mechanics and Rock Engineering, 2021)

Dietary exposure assessment of cadmium, arsenic, and lead in market rice from Sri Lanka - Lin Liu; Jialiang Han; Xiaohang Xu; Zhidong Xu; Kasun S. Abeysinghe; Anjana J. Atapattu; P. Mangala C. S. De Silva; Qinhui Lu; Guangle Qiu (Environmental Science and Pollution Research, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Peripheral ProBDNF Delivered by an AAV Vector to the Muscle Triggers Depression-Like Behaviours in Mice - L. Y. Lin; S. Kelliny; L. C. Liu; M. Al-Hawwas; X. F. Zhou; L. Bobrovskaya (Neurotoxicity Research, 2020)

Zooplankton in a continuous waterscape: environmental and spatial factors shaping spring zooplankton community structure in a large canyon reservoir at the tropic of cancer - Eric Zeus C. Rizo; Ping Liu; Haiyu Niu; Yang Yang; Qiuqi Lin; Rey Donne S. Papa; Henri J. Dumont; Bo-Ping Han (Hydrobiologia, 2020)

A magnetic resonance spectroscopy investigation in symptomatic former NFL players - Michael L. Alosco; Yorghos Tripodis; Benjamin Rowland; Alicia S. Chua; Huijun Liao; Brett Martin; Johnny Jarnagin; Christine E. Chaisson; Ofer Pasternak; Sarina Karmacharya; Inga K. Koerte; Robert C. Cantu; et al. (Brain Imaging and Behavior, 2020)

Climate change considerations are fundamental to management of deep‐sea resource extraction - Lisa A. Levin; Chih‐Lin Wei; Daniel C. Dunn; Diva J. Amon; Oliver S. Ashford; William W. L. Cheung; Ana Colaço; Carlos Dominguez‐Carrió; Elva G. Escobar; Harriet R. Harden‐Davies; Jeffrey C. Drazen; Khaira Ismail; et al. (Global Change Biology, 2020)
Climate change manifestation in the ocean, through warming, oxygen loss, increasing acidification, and changing particulate organic carbon flux (one metric of altered food supply), is projected to affect most deep‐ocean ecosystems concomitantly with increasing direct human disturbance. Climate drivers will alter deep‐sea biodiversity and associated ecosystem services, and may interact with disturbance from resource extraction activities or even climate geoengineering. We suggest that to ensure the effective management of increasing use of the deep ocean (e.g., for bottom fishing, oil and gas extraction, and deep‐seabed mining), environmental management and developing regulations must consider climate change. Strategic planning, impact assessment and monitoring, spatial management, application of the precautionary approach, and full‐cost accounting of extraction activities should embrace climate consciousness. Coupled climate and biological modeling approaches applied in the water and on the seafloor can help accomplish this goal. For example, Earth‐System Model projections of climate‐change parameters at the seafloor reveal heterogeneity in projected climate hazard and time of emergence (beyond natural variability) in regions targeted for deep‐seabed mining. Models that combine climate‐induced changes in ocean circulation with particle tracking predict altered transport of early life stages (larvae) under climate change. Habitat suitability models can help assess the consequences of altered larval dispersal, predict climate refugia, and identify vulnerable regions for multiple species under climate change. Engaging the deep observing community can support the necessary data provisioning to mainstream climate into the development of environmental management plans. To illustrate this approach, we focus on deep‐seabed mining and the International Seabed Authority, whose mandates include regulation of all mineral‐related activities in international waters and protecting the marine environment from the harmful effects of mining. However, achieving deep‐ocean sustainability under the UN Sustainable Development Goals will require integration of climate consideration across all policy sectors.

A System Level Analysis of Coastal Ecosystem Responses to Hurricane Impacts - C. J. Patrick; L. Yeager; A. R. Armitage; F. Carvallo; V. M. Congdon; K. H. Dunton; M. Fisher; A. K. Hardison; J. D. Hogan; J. Hosen; X. Hu; B. Kiel Reese; et al. (Estuaries and Coasts, 2020)

A Major Hydrothermal Reservoir Underneath the Tatun Volcano Group of Taiwan: Clues from a Dense Linear Geophone Array - C. H. Lin; Y. C. Lai; M. H. Shih; C. J. Lin; J. S. Ku; Y. C. Huang (Pure and Applied Geophysics, 2020)
A dense linear geophone array is deployed across the Tatun volcano group (TVG) at the northern tip of Taiwan, where more than 7 million residents live in the Taipei metropolis. The array is composed of 50 geophones with a station spacing of ~ 200 m in average, and it is designed for striking in the NW–SE direction to record the many earthquakes in eastern Taiwan, where the Philippine Sea plate subducted beneath the Eurasia plate. The detailed examination of felt earthquakes shows consistent P-wave delays are recorded at particular stations of the array. The further forward modeling indicates there is a low-velocity zone (LVZ) at depths between ~ 0.5 and ~ 2.5 km beneath the major fumarole sites. Combining this preliminary result with previous studies including clustering seismicity, volcanic earthquakes, low-resistivity zone, strong degassing processes and shallow velocity structures, we suggest that the LVZ might be associated with the major hydrothermal reservoir at the TVG. The identification of the hydrothermal reservoir by the LVZ not only implies a potential volcanic threat, such as phreatic eruptions, in the future, but also provides the possibility of sustainable geothermal resources for replacing traditional nuclear and fossil fuel power plants. Detailed images of the LVZ and other volcanic structures will be obtained soon when dense geophone arrays with more than 600 geophones are deployed from 2020 to 2022.

A deep-level region-based visual representation architecture for detecting strawberry flowers in an outdoor field - P. Lin; W. S. Lee; Y. M. Chen; N. Peres; C. Fraisse (Precision Agriculture, 2020)

A new slice-based method for calculating the minimum safe thickness for a filled-type karst cave - Z. H. Xu; X. Huang; S. C. Li; P. Lin; X. S. Shi; J. Wu (Bulletin of Engineering Geology and the Environment, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Variance in the response of silcrete to rapid heating complicates assumptions about past heat treatment methods - Alex Mackay; Sam C. Lin; Lachlan S. Kenna; Alex F. Blackwood (Archaeological and Anthropological Sciences, 2019)

Bismuth(III) interactions with Desulfovibrio desulfuricans: inhibition of cell energetics and nanocrystal formation of Bi2S3 and Bi0 - Larry L. Barton; Alex S. Granat; Seungyeol Lee; Huifang Xu; Nathaniel L. Ritz; Robert Hider; Henry C. Lin (BioMetals, 2019)

Aeromonas shuberti as a cause of multi‐organ necrosis in internal organs of Nile tilapia, Oreochromis niloticus - C Liu; O Q Chang; D F Zhang; K B Li; F Wang; M H Lin; C B Shi; L Jiang; Q Wang; S M Bergmann (Journal of Fish Diseases, 2018)
A disease with white spots in internal organs of Nile tilapia occurred in Zhanjiang, southern China. Multiple, white nodules, 0.8–2.2 mm in diameter, were scattered throughout the liver, spleen and kidney of diseased fish. Signs of nodules reproduced after artificial infection with the isolated strain. Isolated bacteria were Gram‐negative, facultative anaerobic, motile, short rod‐shaped, with a length of 1.2–2.2 μm. Morphological and biochemical tests, as well as phylogenetic analysis, all strongly indicated that the isolate from tilapia is identical to Aeromonas schubertii ( A. schubertii) which temporary named LF 1708 strain. Antibiotic sensitivity assays showed the LF 1708 is sensitive to 24 of 27 tested antibiotics. Pathogenicity test revealed that the isolate at the dose of 3.75 × 10 6 CFU /g killed 100% of experimental tilapia within 2 days and the dose of 1 × 10 7 CFU /g killed 100% of experimental zebrafish within 1 day. Histopathology of diseased tilapia infected with A. schubertii showed numerous necrotic lesions widely distributed in spleen, liver and kidney, and infiltration with a large number of bacteria. To our knowledge, this was the first report that associated A. schubertii with mortality in tilapia.

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Effects of acute morphine withdrawal on ultrasonic vocalizations in adult rats: unchanged 50-kHz call rate and altered subtype profile - YiQi C. Lin; Leah L. Zhao; Paul B. S. Clarke (Psychopharmacology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Trade-offs between defence and competition in gregarious juvenile fluted giant clams (Tridacna squamosa L.) - Darren Z. H. Sim; Mei Lin Neo; Ambert C. F. Ang; Lynette S. M. Ying; Peter A. Todd (Marine Biology, 2018)

Microbial dolomite in the sabkha environment of the middle Cambrian in the Tarim Basin, NW China - X. L. You; S. Sun; C. S. Lin; J. Q. Zhu (Australian Journal of Earth Sciences, 2018)

Molecular screening of multidrug-resistance tuberculosis by a designated public health laboratory in Taiwan - H.-C. Lin; C.-L. Perng; Y.-W. Lai; F.-G. Lin; C.-J. Chiang; H.-A. Lin; R. Jou; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Development of a two-stage washing and biodegradation system to remediate octachlorinated dibenzo-p-dioxin-contaminated soils - J. L. Lin; C. D. Dong; C. W. Chen; S. H. Chen; T. E. Hsieh; C. M. Kao (International Journal of Environmental Science and Technology, 2017)

Helicobacter pylori infection increases the risk of adult-onset asthma: a nationwide cohort study - Y-C Wang; T-Y Lin; S-T Shang; H-J Chen; C-H Kao; C-C Wu; T-Y Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Formation of chlorite rims and the impact of pore-lining chlorite on reservoir quality: a case study from Shiqianfeng sandstones in upper Permian of Dongpu Depression, Bohai Bay Basin, eastern China - P. J. Ma; C. Y. Lin; S. Q. Zhang; C. M. Dong; Y. F. Xu (Australian Journal of Earth Sciences, 2017)

Evolution of landslide hotspots in Taiwan - S. C. Lin; M. C. Ke; C. M. Lo (Landslides, 2017)

Gonorrhea infection increases the risk of prostate cancer in Asian population: a nationwide population-based cohort study - Y.-C. Wang; C.-H. Chung; J.-H. Chen; M.-H. Chiang; Ti-Yin; C.-H. Tsao; F.-H. Lin; W.-C. Chien; S.-T. Shang; F.-Y. Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Identification of diverse bacterial communities for potential bio-aids capable of troubleshooting for wastewater biological treatment processes - H-W Kuo; C-Y Huang; C-N Chang; P-L Lee; Y-W Chen; C-F Huang; H-H Chang; Y-H Tang; S-Z Zeng; G-Y Li; C-R Lin; L-Z Chen (International Journal of Environmental Science and Technology, 2017)

Variability of hydrological extreme events in East Asia and their dynamical control: a comparison between observations and two high-resolution global climate models - N. Freychet; A. Duchez; C.-H. Wu; C.-A. Chen; H.-H. Hsu; J. Hirschi; A. Forryan; B. Sinha; A. L. New; T. Graham; M. B. Andrews; C.-Y. Tu; et al. (Climate Dynamics, 2017)

Angiopoietins as serum biomarkers for lymphatic anomalies - Timothy D. Le Cras; Paula S. Mobberley-Schuman; Mary Broering; Lin Fei; Cameron C. Trenor; Denise M. Adams (Angiogenesis, 2017)

Changes in Sulforaphane and Selenocysteine Methyltransferase Transcript Levels in Broccoli Treated with Sodium Selenite - K. Huang; J. C. Lin; Q. Y. Wu; J. Y. Yan; M. Y. Liu; S. Zhang; W. J. Xiao (Plant Molecular Biology Reporter, 2016)

Copper(II) binding properties of hepcidin - Kanokwan Kulprachakarn; Yu-Lin Chen; Xiaole Kong; Maria C. Arno; Robert C. Hider; Somdet Srichairatanakool; Sukhvinder S. Bansal (JBIC Journal of Biological Inorganic Chemistry, 2016)

Early detection of Mycobacterium tuberculosis complex in BACTEC MGIT cultures using nucleic acid amplification - S. Y. Lin; S. C. Hwang; Y. C. Yang; C. F. Wang; Y. H. Chen; T. C. Chen; P. L. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Strong inhibition of betanodavirus replication by ribavirin targeting RNA ‐dependent RNA polymerase - Y‐C Huang; T‐S Lin; C Peng; N‐L Chan; Y‐S Han (Journal of Fish Diseases, 2016)

Bismuth(III) deferiprone effectively inhibits growth of Desulfovibrio desulfuricans ATCC 27774 - Larry L. Barton; Daniel A. Lyle; Nathaniel L. Ritz; Alex S. Granat; Ali N. Khurshid; Nada Kherbik; Robert Hider; Henry C. Lin (BioMetals, 2016)

Blockade of CD127 Exerts a Dichotomous Clinical Effect in Marmoset Experimental Autoimmune Encephalomyelitis - Jordon Dunham; Li-Fen Lee; Nikki van Driel; Jon D. Laman; Irene Ni; Wenwu Zhai; Guang-Huan Tu; John C. Lin; Jan Bauer; Bert A. ‘t Hart; Yolanda S. Kap (Journal of Neuroimmune Pharmacology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Histological analysis of somatic embryogenesis in pineapple: AcSERK1 and its expression validation under stress conditions - J. Ma; Y. H. He; Z. Y. Hu; S. Kanakala; W. T. Xu; J. X. Xia; C. H. Guo; S. Q. Lin; C. J. Chen; C. H. Wu; J. L. Zhang (Journal of Plant Biochemistry and Biotechnology, 2016)

Evaluation of soil erosion risk for watershed management in Shenmu watershed, central Taiwan using USLE model parameters - B. S. Lin; K. Thomas; C. K. Chen; H. C. Ho (Paddy and Water Environment, 2016)

Pharmacodynamic Activity of Dapivirine and Maraviroc Single Entity and Combination Topical Gels for HIV-1 Prevention - Charlene S. Dezzutti; Sarah Yandura; Lin Wang; Bernard Moncla; Elizabeth A. Teeple; Brid Devlin; Jeremy Nuttall; Elizabeth R. Brown; Lisa C. Rohan (Pharmaceutical Research, 2015)

Rapid generation and analysis of expressed sequence tags to uncovering inflorescence secondary metabolism of Bougainvillea spectabilis ‘Speciosas’ by pyrosequencing - S. X. Xu; Q. Y. Huang; C. S. Lin; F. C. Lin; L. X. Lin; Q. Y. Shen (Euphytica, 2015)

The influence of shelf-sea fronts on winter monsoon over East China Sea - L.-Y. Oey; M.-C. Chang; S.-M. Huang; Y.-C. Lin; M.-A. Lee (Climate Dynamics, 2015)

Identification and characterization of a late gene encoded by grouper iridovirus 2L (GIV‐2L) - H‐Y Lin; C‐F Cheng; P P Chiou; C‐J Liou; J‐C Yiu; Y‐S Lai (Journal of Fish Diseases, 2015)
Grouper iridovirus (GIV) belongs to the Ranavirus genus and is one of the most important viral pathogens in grouper, particularly at the fry and fingerling stages. In this study, we identified and characterized the GIV‐2L gene, which encodes a protein of unknown function. GIV‐2L is 1242 bp in length, with a predicted protein mass of 46.2 kDa. It displayed significant identity only with members of the Ranavirus and Iridovirus genera. We produced mouse monoclonal antibodies against the GIV‐2L protein by immunizing mice with GIV‐2L‐His‐tag recombinant protein. By inhibiting de novo protein and DNA synthesis in GIV‐infected cells, we showed that GIV‐2L was a late gene during the viral replication. Finally, immunofluorescence microscopy revealed that GIV‐2L protein accumulated in both the nucleus and cytoplasm of infected cells. These results offer important insights into the pathogenesis of GIV.

Crustal thickening and extension induced by the Great Sumatra–Andaman earthquake of 26 December 2004: revealed by the seismic moment tensor element Mrr - J.-Y. Lin; C.-L. Lo; W.-N. Wu; J.-C. Sibuet; S.-K. Hsu; Y.-Y. Wen (Marine Geophysical Research, 2015)

Ambient air concentrations of PCDD/Fs, coplanar PCBs, PBDD/Fs, and PBDEs and their impacts on vegetation and soil - Y.-C. Kuo; Y.-C. Chen; M.-Y. Lin; L.-H. Young; H.-T. Hsu; S.-H. Liou; T.-N. Wu; L.-C. Wang; P.-J. Tsai (International Journal of Environmental Science and Technology, 2015)

Statins can increase the risk of herpes zoster infection in Asia - H.-H. Chen; C.-L. Lin; C.-J. Yeh; S.-Y. Yeh; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Clustering of Clinical and Environmental Escherichia coli O104 Isolates Using the DiversiLab™ Repetitive Sequence-Based PCR System - N. M. Herbold; L. M. Clotilde; K. M. Anderson; J. Kase; G. L. Hartman; S. Himathongkham; A. Lin; C. R. Lauzon (Current Microbiology, 2015)

Clinical manifestations and prognostic factors of Morganella morganii bacteremia - T.-Y. Lin; M.-C. Chan; Y.-S. Yang; Y. Lee; K.-M. Yeh; J.-C. Lin; F.-Y. Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Establishment of a novel, eco-friendly transgenic pig model using porcine pancreatic amylase promoter-driven fungal cellulase transgenes - Y. S. Lin; C. C. Yang; C. C. Hsu; J. T. Hsu; S. C. Wu; C. J. Lin; W. T. K. Cheng (Transgenic Research, 2015)

Genetic variation in estrogen and progesterone pathway genes and breast cancer risk: an exploration of tumor subtype-specific effects - Sarah J. Nyante; Marilie D. Gammon; Jay S. Kaufman; Jeannette T. Bensen; Dan Yu Lin; Jill S. Barnholtz-Sloan; Yijuan Hu; Qianchuan He; Jingchun Luo; Robert C. Millikan (Cancer Causes & Control, 2015)

Accumulation of arsenic in rice plant: a study of an arsenic-contaminated site in Taiwan - S.-C. Lin; T.-K. Chang; W.-D. Huang; H.-S. Lur; G.-S. Shyu (Paddy and Water Environment, 2015)

Transynaptic Changes Evident in Peripheral Axonal Function After Acute Cerebellar Infarct - William Huynh; Cindy S-Y. Lin; Arun V. Krishnan; Steve Vucic; Matthew C. Kiernan (The Cerebellum, 2014)

AdeRS combination codes differentiate the response to efflux pump inhibitors in tigecycline-resistant isolates of extensively drug-resistant Acinetobacter baumannii - J.-R. Sun; C.-L. Perng; J.-C. Lin; Y.-S. Yang; M.-C. Chan; T.-Y. Chang; F.-M. Lin; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Characterization of baseline sensitivity and resistance risk of Colletotrichum gloeosporioides complex isolates from strawberry and grape to two demethylation-inhibitor fungicides, prochloraz and tebuconazole - X. F. Xu; T. Lin; S. K. Yuan; D. J. Dai; H. J. Shi; C. Q. Zhang; H. D. Wang (Australasian Plant Pathology, 2014)

The first record, tagging and release of a neonatal whale shark Rhincodon typus in Taiwan - H. H. Hsu; C. Y. Lin; S. J. Joung (Journal of Fish Biology, 2014)
On 27 October 2013, a Rhincodon typus was apparently chased by a group of Caranx ignobilis into nearshore waters near Green Island (Ludao), east of Taiwan. A fisherman brought it back to port where it was kept in a small sea pen until release. The R. typus was 78 cm total length, and was tagged and released on 29 October 2013.

Association between herpes zoster and end stage renal disease entrance in chronic kidney disease patients: a population-based cohort study - S.-Y. Lin; J.-H. Liu; H.-C. Yeh; C.-L. Lin; I.-J. Tsai; P.-C. Chen; F.-C. Sung; Y.-F. Yang; C.-C. Huang; D. E. Morisky; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

The association between chronic osteomyelitis and increased risk of diabetes mellitus: a population-based cohort study - S.-Y. Lin; C.-L. Lin; C.-H. Tseng; I.-K. Wang; S.-M. Wang; C.-C. Huang; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Erratum to: Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study - S.-Y. Tsai; T.-Y. Yang; H.-J. Chen; C.-S. Chen; W.-M. Lin; W.-C. Shen; C.-N. Kuo; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Increased risk of pulmonary tuberculosis among patients with appendectomy in Taiwan - S.-W. Lai; C.-L. Lin; K.-F. Liao; S.-M. Tsai (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study - S.-Y. Tsai; T.-Y. Yang; H.-J. Chen; C.-S. Chen; W.-M. Lin; W.-C. Shen; C.-N. Kuo; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Molecular characterization of a new member of the 16SrV group of phytoplasma associated with Bischofia polycarpa (Levl.) Airy Shaw witches’ -broom disease in China by a multiple gene-based analysis - F. Lai; C. S. Song; Z. G. Ren; C. L. Lin; Q. C. Xu; Y. Li; C. G. Piao; S. S. Yu; M. W. Guo; G. Z. Tian (Australasian Plant Pathology, 2014)

Development of a selective and differential medium for capsulated L actococcus garvieae - C‐I Chang; C‐F Lee; J‐M Tsai; C‐C Wu; L‐H Chen; S‐C Chen; K‐J Lin (Journal of Fish Diseases, 2014)
A selective and differential medium termed ‘ LG agar’ was developed for the isolation and presumptive identification of L actococcus garvieae that results in black colonies with red halos. In this study, all 14 strains of L . garvieae and only 9 of the 148 strains representing 38 other species were able to grow on the LG agar. The nine viable strains on LG agar plates (including E nterococcus faecalis , E nterococcus faecium , L actococcus lactis , V ibrio fluvialis , V ibrio furnissii , V ibrio mimicus and V ibrio salmonicida ) were further differentiated from L . garvieae by various colours or colony features. Colonies isolated from the mixing culture and the infected giant sea perch using LG agar plates were all positively identified as L . garvieae by conventional tests and 16 S r DNA sequencing. Furthermore, LG agar discriminated capsulated strains of L . garvieae , which were believed to be correlated with pathogens of fish and shellfish, from non‐capsulated ones by colony appearances. The specificity and differentiating ability of LG agar suggest that this medium displays considerable potential for primary isolation and presumptive identification of L . garvieae from pathological and environmental samples.

Characterization, tissue distribution and regulation of neuropeptideY in Schizothorax prenanti - R. Wei; C. Zhou; D. Yuan; T. Wang; F. Lin; H. Chen; H. Wu; Z. Xin; S. Yang; Y. Wang; D. Chen; J. Liu; et al. (Journal of Fish Biology, 2014)
In this study, the full‐length neuropeptide Y ( npy ) complementary (c) DNA was cloned in ya fish Schizothorax prenanti . npy cDNA was composed of 789 nucleotides with a 288 nucleotide open reading frame encoding a protein of 96 amino acids. The deduced amino acid sequences contained a 28 amino acids signal peptide followed by a 36 amino acids mature neuropeptide Y (NPY). The npy mRNA was expressed mainly in the brain and eye as detected by real‐time quantitative polymerase chain reaction RT‐PCR ( rt‐qPCR ). The S. prenanti NPY was detectable from blastulation to hatch, suggesting that npy might be involved in the late embryonic development of S. prenanti . An experiment was conducted to determine the expression profile of npy during feeding of a single meal and during long‐term fasting. The expression level of npy in fed fish was significantly decreased at 0·5, 1·5, 3 and 9 h post‐feeding (hpf) than in fasting fish. Fasting for 14 days induced an increase in npy messenger (m) RNA expression in the brain. Overall, the results suggest that NPY is a conserved peptide that might be involved in the regulation of feeding and other physiological function in S. prenanti .

Characterization of Schizothorax prenanti cgnrhII gene: fasting affects cgnrhII expression - T. Wang; D. Yuan; C. Zhou; F. Lin; H. Chen; H. Wu; R. Wei; Z. Xin; J. Liu; Y. Gao; D. Chen; S. Yang; et al. (Journal of Fish Biology, 2014)
In this study, the role of chicken gonadotropin‐releasing hormone II ( cgnrhII ) in feeding regulation was investigated in Schizothorax prenanti . First, the full‐length S. prenanti cgnrhII cDNA consisted of 693 bp with an open reading frame of 261 bp encoding a protein of 86 amino acids. Next, cgnrhII was widely expressed in the central and peripheral tissues. Last, there were significant changes in cgnrhII mRNA expression in the fasted group compared to the fed group in the S. prenanti hypothalamus during 24 h fasting ( P cgnrhII gene expression presented a significant decrease in the fasted group compared with the fed group ( P cgnrhII mRNA expression level between refed and fed group on day 9 ( P > 0·05). Thus, the results suggest that cGnRH II expression is influenced by fasting and the gene may be involved in feeding regulation in S. prenanti.

Mechanism-Based Pharmacokinetic Modeling to Evaluate Transporter-Enzyme Interplay in Drug Interactions and Pharmacogenetics of Glyburide - Manthena V. S. Varma; Renato J. Scialis; Jian Lin; Yi-An Bi; Charles J. Rotter; Theunis C. Goosen; Xin Yang (The AAPS Journal, 2014)

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

Effects of Dietary Selenium Deficiency on mRNA Levels of Twenty-One Selenoprotein Genes in the Liver of Layer Chicken - C. P. Liu; J. Fu; S. L. Lin; X. S. Wang; S. Li (Biological Trace Element Research, 2014)

Early Airway Structural Changes in Cystic Fibrosis Pigs as a Determinant of Particle Distribution and Deposition - Maged Awadalla; Shinjiro Miyawaki; Mahmoud H. Abou Alaiwa; Ryan J. Adam; Drake C. Bouzek; Andrew S. Michalski; Matthew K. Fuld; Karen J. Reynolds; Eric A. Hoffman; Ching-Long Lin; David A. Stoltz (Annals of Biomedical Engineering, 2014)

Lasting neurobehavioral abnormalities in rats after neonatal activation of serotonin 1A and 1B receptors: possible mechanisms for serotonin dysfunction in autistic spectrum disorders - Nidhi Khatri; Kimberly L. Simpson; Rick C. S. Lin; Ian A. Paul (Psychopharmacology, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Motor Cortex Excitability in Acute Cerebellar Infarct - William Huynh; Arun V. Krishnan; Steve Vucic; Cindy S-Y. Lin; Matthew C. Kiernan (The Cerebellum, 2013)

White spot syndrome virus epizootic in cultured P acific white shrimp L itopenaeus vannamei (Boone) in T aiwan - L Cheng; W‐H Lin; P‐C Wang; M‐A Tsai; J‐P Hsu; S‐C Chen (Journal of Fish Diseases, 2013)
White spot syndrome virus ( WSSV ) has caused significant losses in shrimp farms worldwide. Between 2004 and 2006, Pacific white shrimp L itopenaeus vannamei (Boone) were collected from 220 farms in T aiwan to determine the prevalence and impact of WSSV infection on the shrimp farm industry. Polymerase chain reaction ( PCR ) analysis detected WSSV in shrimp from 26% of farms. Juvenile shrimp farms had the highest infection levels (38%; 19/50 farms) and brooder shrimp farms had the lowest (5%; one of 20 farms). The average extent of infection at each farm was as follows for WSSV ‐positive farms: post‐larvae farms, 71%; juvenile farms, 61%; subadult farms, 62%; adult farms, 49%; and brooder farms, 40%. Characteristic white spots, hypertrophied nuclei and basophilic viral inclusion bodies were found in the epithelia of gills and tail fans, appendages, cephalothorax and hepatopancreas, and virions of WSSV were observed. Of shrimp that had WSSV lesions, 100% had lesions on the cephalothorax, 96% in gills and tail fans, 91% on appendages and 17% in the hepatopancreas. WSSV was also detected in copepoda and crustaceans from the shrimp farms. Sequence comparison using the pms146 gene fragment of WSSV showed that isolates from the farms had 99.7–100% nucleotide sequence identity with four strains in the G en B ank database – China ( AF332093 ), T aiwan ( AF440570 and U50923 ) and Thailand ( AF369029 ). This is the first broad study of WSSV infection in L . vannamei in T aiwan.

Core–shell magnetite-silica dithiocarbamate-derivatised particles achieve the Water Framework Directive quality criteria for mercury in surface waters - C. B. Lopes; P. Figueira; D. S. Tavares; Z. Lin; A. L. Daniel-da-Silva; A. C. Duarte; J. Rocha; T. Trindade; E. Pereira (Environmental Science and Pollution Research, 2013)

Soluble interleukin‐1 receptor, a potential negative regulator of orange‐spotted grouper Epinephelus coioides interleukin‐1 system - D. Q. Lu; M. Yao; S. B. Yi; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2013)
In this study, the cDNA sequence encoding interleukin‐1 ( Il ‐1) receptor‐like protein of orange‐spotted grouper Epinephelus coioides was obtained. The newly identified sequence was named soluble type I Il ‐1 receptor ( sIl‐1rI ) owing to its structural composition, which had two Ig‐like domains, lack of transmembrane region and the Toll/interleukin‐1 receptor ( TIR ) domain, similar to the brown rat Rattus norvegicus soluble Il‐1rI . In addition, sequence comparison and phylogenetic analysis indicated that E. coioides sequence had a closer relationship with Il‐1rI than Il‐1rII . Real‐time PCR revealed that sil‐1rI mRNA expression presented a process of decrease, restoration and increase in Cryptocaryon irritans ‐infected E. coioides . The negative correlation between Il ‐1β and sil‐1rI mRNA in C. irritans ‐infected head‐kidney implied the potential negative regulatory role of sil‐1rI in E. coioides Il ‐1 system. The leucocytes incubated with lipopolysaccharide or polyriboinosinic polyribocytidylic acid exhibited different expression profiles of sil‐1rI . Recombinant Il ‐1β ( rIl ‐1β) protein was capable of inducing sil‐1rI mRNA under the concentration of 100 ng ml −1 , suggesting that high dosage or excess Il ‐1β would stimulate the expression of sil‐1rI to maintain the homoeostasis of E. coioides Il ‐1 system. For the first time, the role of teleost Il‐1rI in parasite infection has been identified, and soluble Il‐1r was found in fish.

Warming up to climate change: a participatory approach to engaging with agricultural stakeholders in the Southeast US - Wendy-Lin Bartels; Carrie A. Furman; David C. Diehl; Fred S. Royce; Daniel R. Dourte; Brenda V. Ortiz; David F. Zierden; Tracy A. Irani; Clyde W. Fraisse; James W. Jones (Regional Environmental Change, 2013)

The use of procalcitonin in the diagnosis of bone and joint infection: a systemic review and meta-analysis - C.-J. Shen; M.-S. Wu; K.-H. Lin; W.-L. Lin; H.-C. Chen; J.-Y. Wu; M. C.-H. Lee; C.-C. Lee (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Characterization of a novel cell line from the caudal fin of koi carp Cyprinus carpio - S.‐L. Lin; Y.‐H. Cheng; C.‐M. Wen; S.‐N. Chen (Journal of Fish Biology, 2013)
A continuous cell line ( KF ‐101) derived from the caudal fin of the koi carp Cyprinus carpio was established and characterized. The KF ‐101 cell line multiplied abundantly in Leibovitz's L‐15 medium containing 10% foetal bovine serum at 25° C, and was subcultured for >90 passages over a period of 3 years. Immunocytochemistry revealed that the KF ‐101 cells contain keratin, junction proteins connexin‐43 and occludin, and ectodermal stem‐cell marker Pax‐6, but not vimentin. Furthermore, the KF ‐101 cells reacted with anti‐human DARPP ‐32 and anti‐human GATA ‐4 antibodies, and the labelling was regulated according to the cell cycle. The labels of the DARPP ‐32 and GATA ‐4 antibodies in the KF ‐101 cells were the suggested phosphatase‐1 inhibitor‐1 and GATA ‐3, respectively. In addition, the KF ‐101 cells were susceptible to koi herpesvirus but were resistant to eel herpesvirus, iridovirus, grouper nodavirus and chum salmon ( Oncorhynchus keta ) virus. The results indicate that the KF ‐101 cells are suitable materials for investigating biological and virological development.

Seismic health monitoring of RC frame structures using smart aggregates - Wen-I Liao; C. H. Lin; J. S. Hwang; G. Song (Earthquake Engineering and Engineering Vibration, 2013)

Sex identification in the Collared Scops Owl (Otus bakkamoena) with novel markers generated by random amplified polymorphic DNA - P. H. Wang; H. A. Hsu; M. C. Chao; F. T. Chan; L. M. Wang; P. I. Lin; H. S. Tsao; H. W. Yuan; C. C. Chen; S. T. Ding (Conservation Genetics Resources, 2013)

Climate trends in indices for temperature and precipitation across New York State, 1948–2008 - T. Z. Insaf; S. Lin; S. C. Sheridan (Air Quality, Atmosphere & Health, 2013)

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG) - Jianfeng Xu; Ethan M. Lange; Lingyi Lu; Siqun L. Zheng; Zhong Wang; Stephen N. Thibodeau; Lisa A. Cannon-Albright; Craig C. Teerlink; Nicola J. Camp; Anna M. Johnson; Kimberly A. Zuhlke; Janet L. Stanford; et al. (Human Genetics, 2013)

Development of microsatellite markers in an ungulate mammal, the Formosan serow (Capricornis swinhoei) - Y. Y. Chang; M. C. Chao; S. T. Ding; E.-C. Lin; H. S. Tsao; H. W. Yuan; P. H. Wang (Conservation Genetics Resources, 2012)

Characterization of carbapenem-nonsusceptible Klebsiella pneumoniae bloodstream isolates at a Taiwanese hospital: clinical impacts of lowered breakpoints for carbapenems - N. Y. Lee; J. J. Wu; S. H. Lin; W. C. Ko; L. H. Tsai; J. J. Yan (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Regional variation in otolith Sr:Ca ratios of African longfinned eel Anguilla mossambica and mottled eel Anguilla marmorata : a challenge to the classic tool for reconstructing migratory histories of fishes - Y.‐J. Lin; B. M. Jessop; O. L. F. Weyl; Y. Iizuka; S.‐H. Lin; W.‐N. Tzeng; C.‐L. Sun (Journal of Fish Biology, 2012)
Otolith Sr:Ca ratios of the African longfinned eel Anguilla mossambica and giant mottled eel Anguilla marmorata from nine freshwater sites in four rivers of South Africa were analysed to reconstruct their migratory life histories between freshwater and saltwater habitats. For A. mossambica , the Sr:Ca ratios in the otolith edge differed significantly among rivers and had large effect sizes, but did not differ among sites within a river. Otolith Sr:Ca ratios did not differ among rivers for A. marmorata . When rivers were pooled, the edge Sr:Ca ratios of A. mossambica were not significantly different from those of A. marmorata . According to the river‐specific critical Sr:Ca ratio distinguishing freshwater from saltwater residence, most A. mossambica and A. marmorata had saltwater habitat experience after settlement in fresh water. This was primarily during their elver stage or early in the yellow eel stage. During the middle and late yellow eel stage, freshwater residency was preferred and only sporadic visits were made to saltwater habitats. The data also suggest that regional variations in otolith Sr:Ca ratios affect the critical Sr:Ca value and are a challenge for the reconstruction of migratory life histories that should be explicitly considered to avoid bias and uncertainty.

Identification and expression analysis of major histocompatibility complex IIB gene in orange‐spotted grouper Epinephelus coioides - D. Q. Lu; S. B. Yi; M. Yao; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2012)
In this study, complementary DNA (cDNA) and DNA sequences of major histocompatibility complex (MHC) class IIB genes ( mhcIIB ) were cloned from orange‐spotted grouper Epinephelus coioides . The gene structure of E. coioides mhcIIB consists of five exons and four introns, and its deduced amino acid sequence length is 249 amino acids, including a signal peptide, a peptide‐binding region, an IGC1 domain, a transmembrane region and a cytoplasmic tail. A phylogenetic study showed that E. coioides mhcIIB shared 32·0–79·1% identity with those of other teleosts and mammals. Real‐time reverse transcriptase (RT)‐PCR was performed to detect the class IIB gene expression in eight different tissues. To characterize the relationship between E. coioides mhcIIB gene and pathogens, in vivo and in vitro studies were performed. Challenge of Cryptocaryon irritans revealed that class IIB genes were down‐regulated after 24 and 48 h of challenge, and their expression was later restored at 72 h. Stimulation of isolated E. coioides leukocytes with lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (PolyI:C) significantly increased peripheral blood and spleen mhcIIB expression, while head kidney mhcIIB expression remained constant.

Reemerging of enterovirus 71 in Taiwan: the age impact on disease severity - S.-M. Wang; T.-S. Ho; H.-C. Lin; H.-Y. Lei; J.-R. Wang; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

A review of magnetic resonance imaging and diffusion tensor imaging findings in mild traumatic brain injury - M. E. Shenton; H. M. Hamoda; J. S. Schneiderman; S. Bouix; O. Pasternak; Y. Rathi; M.-A. Vu; M. P. Purohit; K. Helmer; I. Koerte; A. P. Lin; C.-F. Westin; et al. (Brain Imaging and Behavior, 2012)

Seasonal Variation and Health Risk Assessment of Polycyclic Aromatic Hydrocarbons in Miaoli City, Taiwan - C. C. Wu; T. S. Lin; T. T. Yang; H. W. Hsu; C. L. Chang; C. H. Huang; W. Y. Lin (Bulletin of Environmental Contamination and Toxicology, 2012)

Spatial dependence of alveolar angiogenesis in post-pneumonectomy lung growth - Moritz A. Konerding; Barry C. Gibney; Jan P. Houdek; Kenji Chamoto; Maximilian Ackermann; Grace S. Lee; Miao Lin; Akira Tsuda; Steven J. Mentzer (Angiogenesis, 2012)

Differential expression profiling of orange‐spotted grouper larvae, Epinephelus coioides (Hamilton), that survived a betanodavirus outbreak - M‐S Wu; C‐W Chen; C‐H Lin; C‐S Tzeng; C‐Y Chang (Journal of Fish Diseases, 2012)
Nervous necrosis virus (NNV), a piscine nodavirus, has caused serious viral nervous necrosis and viral encephalopathy and retinopathy in hatchery‐reared larvae and juveniles of a wide range of marine teleost species worldwide in the last two decades. Although the mortality of NNV‐infected larvae is nearly 100%, there are still some larvae that survive this catastrophe. To comprehensively understand the variations of these survivors at the molecular level, we collected orange‐spotted grouper larvae that survived an NNV outbreak in an indoor hatchery in southern Taiwan to study differential gene expression. Healthy larvae with high, medium and low levels of detected NNV were compared with morbid larvae using a 9600‐clone‐containing grouper larva cDNA microarray, and differential gene expression was further confirmed by a quantitative real‐time polymerase chain reaction. Significant variation exists in healthy larvae. The following genes were upregulated: adenylate kinase 1‐2, myosin binding protein H‐like, myosin light chain 2, myosin light chain 3, tropomyosin, fast/white muscle troponin T embryonic isoform, and parvalbumin 1 and 2 genes. The following genes were downregulated: apolipoprotein A‐I, trypsinogen, pyruvate kinase and astacin‐like metalloprotease. Moreover, immunoglobulin M heavy chain gene transcription was significantly higher in healthy larvae that had high virus levels, indicating that humoral immunity might protect organisms from viral infection. These results suggest that some non‐immune‐related genes may have played important roles in survival during the larval metamorphosis stage, after betanodavirus infection.

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Arsenic content, fractionation, and ecological risk in the surface sediments of lake - S. L. Wang; C. Y. Lin; X. Z. Cao; X. Zhong (International Journal of Environmental Science and Technology, 2012)

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Bacteremia caused by Brevundimonas species at a tertiary care hospital in Taiwan, 2000–2010 - M. R. Lee; Y. T. Huang; C. H. Liao; T. Y. Chuang; C. K. Lin; S. W. Lee; C. C. Lai; C. J. Yu; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Assessment of nitrogen contamination of groundwater in paddy and upland fields - Y. H. Kao; C.-W. Liu; C. S. Jang; S. W. Zanh; K. H. Lin (Paddy and Water Environment, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Learning Through Service: Student Perceptions on Volunteering at Interprofessional Hepatitis B Student-run Clinics - Leslie C. Sheu; Patricia Zheng; Anabelle D. Coelho; Lisa D. Lin; Patricia S. O’Sullivan; Bridget C. O’Brien; Albert Y. Yu; Cindy J. Lai (Journal of Cancer Education, 2011)

Diagnostic performance of an enzyme-linked immunospot assay for interferon-γ in skeletal tuberculosis - C.-C. Lai; C.-K. Tan; W.-L. Liu; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Clinical significance of nontuberculous mycobacteria isolates in elderly Taiwanese patients - C.-C. Lai; C. K. Tan; S. H. Lin; W. L. Liu; C. H. Liao; Y. T. Huang; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

The controlled in vitro susceptibility of gastrointestinal pathogens to the antibacterial effect of manuka honey - S. M. Lin; P. C. Molan; R. T. Cursons (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Quantitative trait loci for temperature-sensitive resistance to Puccinia striiformis f. sp. tritici in wheat cultivar Flinor - J. Feng; L. L. Zuo; Z. Y. Zhang; R. M. Lin; Y. Y. Cao; S. C. Xu (Euphytica, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

Urban China in transformation: Hybrid economy, juxtaposed space, and new testing ground for geographical enquiries - George C S Lin (Chinese Geographical Science, 2011)

Mobilization and transport of coarse woody debris to the oceans triggered by an extreme tropical storm - A. J. West; C.-W. Lin; T.-C. Lin; R. G. Hilton; S.-H. Liu; C.-T. Chang; K.-C. Lin; A. Galy; R. B. Sparkes; N. Hovius (Limnology and Oceanography, 2011)
A significant consequence of Typhoon Morakot in August 2009 was the production of vast volumes of driftwood in Pacific Asia. We have quantified the flux of this coarse woody debris (CWD) to the oceans from typhoon‐triggered landslides in Taiwan, where Morakot made landfall, by combining remote sensing (using FORMOSAT‐2 imagery and aerial photography), analysis of forest biomass, and field observations. A total of 3.8–8.4 Tg CWD was transported to the oceans, carrying 1.8–4.0 Tg of organic carbon. In addition to the local effects on the marine and coastal environment from such a highly concentrated flux of carbon and nutrients, storm‐driven mobilization of CWD may represent a significant, if infrequent, transfer of terrestrial biomass to the oceans. If the frequency of relatively rare, extreme storms such as Morakot increases in a changing climate, this transport mechanism may play an important role in feedbacks between global climate, storm intensity, and carbon cycling.

QTL analysis and candidate gene mapping for skin and flesh color in sweet cherry fruit (Prunus avium L.) - Suneth S. Sooriyapathirana; Amjad Khan; Audrey M. Sebolt; Dechun Wang; Jill M. Bushakra; Kui Lin-Wang; Andrew C. Allan; Susan E. Gardiner; David Chagné; Amy F. Iezzoni (Tree Genetics & Genomes, 2010)

Groundwater Assessment at Manukan Island, Sabah: Multidisplinary Approaches - S. M. Praveena; C. Y. Lin; A. Z. Aris; M. H. Abdullah (Natural Resources Research, 2010)

Genetic polymorphisms of the DNA repair geneMPG may be associated with susceptibility to rheumatoid arthritis - S. Y. Chen; L. Wan; C. M. Huang; Y. C. Huang; J. J. C. Sheu; Y. J. Lin; S. P. Liu; Y. C. Lan; C. H. Lai; C. W. Lin; C. H. Tsai; F. J. Tsai (Journal of Applied Genetics, 2010)

Declining drug resistance of Mycobacterium tuberculosis isolates from elderly patients in Taiwan, 2000–2008 - W.-L. Liu; C.-C. Lai; C.-K. Tan; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Tikhonov adaptively regularized gamma variate fitting to assess plasma clearance of inert renal markers - Carl A. Wesolowski; Richard C. Puetter; Lin Ling; Paul S. Babyn (Journal of Pharmacokinetics and Pharmacodynamics, 2010)

Ecological Restoration of Polluted Plain Rivers Within the Haihe River Basin in China - W. Wang; X. Q. Tang; S. L. Huang; S. H. Zhang; C. Lin; D. W. Liu; H. J. Che; Q. Yang; Miklas Scholz (Water, Air, & Soil Pollution, 2010)

Cultivation‐independent characterization of ‘ Candidatus Magnetobacterium bavaricum’ via ultrastructural, geochemical, ecological and metagenomic methods - C. Jogler; M. Niebler; W. Lin; M. Kube; G. Wanner; S. Kolinko; P. Stief; A. J. Beck; D. de Beer; N. Petersen; Y. Pan; R. Amann; et al. (Environmental Microbiology, 2010)
Summary ‘ Candidatus Magnetobacterium bavaricum’ is unusual among magnetotactic bacteria (MTB) in terms of cell size (8–10 µm long, 1.5–2 µm in diameter), cell architecture, magnetotactic behaviour and its distinct phylogenetic position in the deep‐branching Nitrospira phylum. In the present study, improved magnetic enrichment techniques permitted high‐resolution scanning electron microscopy and energy dispersive X‐ray analysis, which revealed the intracellular organization of the magnetosome chains. Sulfur globule accumulation in the cytoplasm point towards a sulfur‐oxidizing metabolism of ‘ Candidatus M. bavaricum’. Detailed analysis of ‘ Candidatus M. bavaricum’ microhabitats revealed more complex distribution patterns than previously reported, with cells predominantly found in low oxygen concentration. No correlation to other geochemical parameters could be observed. In addition, the analysis of a metagenomic fosmid library revealed a 34 kb genomic fragment, which contains 33 genes, among them the complete rRNA gene operon of ‘ Candidatus M. bavaricum’ as well as a gene encoding a putative type IV RubisCO large subunit.

The chondroprotective effects of ferulic acid on hydrogen peroxide-stimulated chondrocytes: inhibition of hydrogen peroxide-induced pro-inflammatory cytokines and metalloproteinase gene expression at the mRNA level - M. P. Chen; S. H. Yang; C. H. Chou; K. C. Yang; C. C. Wu; Y. H. Cheng; Feng-Huei Lin (Inflammation Research, 2010)

Clinical and microbiological characteristics of community-acquired thoracic empyema or complicated parapneumonic effusion caused by Klebsiella pneumoniae in Taiwan - Y.-T. Lin; T.-L. Chen; L. K. Siu; S.-F. Hsu; C.-P. Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Positive culture for Klebsiella pneumoniae in relevant sputum samples as a predictor of rapidly fatal outcome in septic patients at medical intensive care units - T.-Y. Chuang; C.-J. Lin; T.-C. Chou; H.-H. Huang; S.-W. Lee; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Optimization of product line design for environmentally conscious technologies in notebook industry - K. H. Lin; L. H. Shih; S. C. Lee (International Journal of Environmental Science and Technology, 2010)

Antibacterial effect of electrolysed acid water on the nasal discharge from patients with chronic rhinosinusitis - R.-S. Jiang; S.-H. Wu; K.-L. Liang; J.-F. Lin; M.-C. Su; W.-K. Chen; F.-J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Clinical and genotypic characteristics of extensively drug-resistant and multidrug-resistant tuberculosis - C. C. Lai; C. K. Tan; S. H. Lin; C. H. Liao; Y. T. Huang; C. H. Chou; H. L. Hsu; C. Y. Wang; H. I. Lin; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Molecular phylogeny of three ambiguous ciliate genera: Kentrophoros , Trachelolophos and Trachelotractus (Alveolata, Ciliophora) - Shan Gao; Michaela C. Strüder-Kypke; Khaled A. S. Al-Rasheid; Xiaofeng Lin; Weibo Song (Zoologica Scripta, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Impact of pneumococcal vaccines on invasive pneumococcal disease in Taiwan - W.-H. Liao; S.-H. Lin; C.-C. Lai; C.-K. Tan; C.-H. Liao; Y.-T. Huang; C.-Y. Wang; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

In vitro activities of doripenem and other carbapenems against clinically important bacteria isolated in intensive care units: nationwide data from the SMART Programme - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Velocity structure and gas hydrate saturation estimation on active margin off SW Taiwan inferred from seismic tomography - Win-Bin Cheng; S. S. Lin; T. K. Wang; C. S. Lee; C. S. Liu (Marine Geophysical Research, 2010)

Tri-directional shaking table tests of vibration sensitive equipment with static dynamics interchangeable-ball pendulum system - C. S. Tsai; Yung-Chang Lin; Wen-Shin Chen; H. C. Su (Earthquake Engineering and Engineering Vibration, 2010)

Artificial neural network analysis for reliability prediction of regional runoff utilization - S. C. Lee; H. T. Lin; T. Y. Yang (Environmental Monitoring and Assessment, 2010)

Establishment, characterization, virus susceptibility and transfection of cell lines from cobia, Rachycentron canadum (L.), brain and fin - T‐C Cheng; Y‐S Lai; I‐Y Lin; C‐P Wu; S‐L Chang; T‐I Chen; M‐S Su (Journal of Fish Diseases, 2010)
Establishment and characterization of two cobia, Rachycentron canadum, cell lines derived from cobia brain (CB) and cobia fin (CF) are described. Caudal fin and brain from juvenile cobia were dissociated for 30 and 10 min, respectively, in phosphate‐buffered saline containing 0.25% trypsin at 25 °C. The optimal culture condition for both dissociated cells (primary cell culture) was at 28 °C in Leibovitz‐15 medium containing 10% foetal bovine serum. The cells have been sub‐cultured at a ratio of 1:2 for more than 160 passages over a period of 3 years. Origin of the cultured cells was verified by comparison of their sequences of mitochondrial cytochrome oxidase subunit I genes ( cox I ) with the cox 1 sequence from cobia muscle tissue. The cell lines showed polyploidy. No mycoplasma contamination was detected. Susceptibility to grouper iridovirus was observed for the CB cell line but not the CF cell line. Both cell lines expressed green fluorescent protein after being transfected with green fluorescent reporter gene driven by the cytomegalovirus promoter.

Identification of three immunodominant regions on leukotoxin protein of Fusobacterium necrophorum - D. B. Sun; R. Wu; G. L. Li; J. S. Zheng; X. P. Liu; Y. C. Lin; D. H. Guo (Veterinary Research Communications, 2009)

Mathematical modeling and full-scale shaking table tests for multi-curve buckling restrained braces - C. S. Tsai; Yungchang Lin; Wenshin Chen; H. C. Su (Earthquake Engineering and Engineering Vibration, 2009)

Nationwide surveillance of antimicrobial resistance among Haemophilus influenzae and Streptococcus pneumoniae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

The in vitro susceptibility of Campylobacter spp. to the antibacterial effect of manuka honey - S. M. Lin; P. C. Molan; R. T. Cursons (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

A quick and efficient approach for gene silencing by using triple putative microRNA-based short hairpin RNAs - Z. X. Shan; Q. X. Lin; M. Yang; C. Y. Deng; S. J. Kuang; Z. L. Zhou; D. Z. Xiao; X. Y. Liu; S. G. Lin; X. Y. Yu (Molecular and Cellular Biochemistry, 2009)

Nationwide surveillance of antimicrobial resistance among Enterobacteriaceae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

High-frequency direct somatic embryogenesis from leaf tissues of Drimiopsis kirkii Baker (giant squill) - T. H. Lan; P. I. Hong; C. C. Huang; W. C. Chang; C. S. Lin (In Vitro Cellular & Developmental Biology - Plant, 2009)

Group A streptococcal infection caused by emm1 strains among children in southern Taiwan - H.-C. Lin; S.-M. Wang; Y.-L. Lin; Y.-S. Lin; J.-J. Wu; W.-J. Chuang; M. T. Lin; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Induction potential of clavulanic acid toward L1 and L2 β-lactamases of Stenotrophomonas maltophilia - C.-W. Lin; R.-M. Hu; S.-C. Huang; Y.-J. Hsiao; T.-C. Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Mapping chromosomal regions affecting flowering time in a spring wheat RIL population - F. Lin; S. L. Xue; D. G. Tian; C. J. Li; Y. Cao; Z. Z. Zhang; C. Q. Zhang; Z. Q. Ma (Euphytica, 2008)

DC-SIGN and L-SIGN: the SIGNs for infection - Ui-Soon Khoo; Kelvin Y. K. Chan; Vera S. F. Chan; C. L. Steve Lin (Journal of Molecular Medicine, 2008)

Ethmoid sinus mycology of chronic rhinosinusitis - R. S. Jiang; K. L. Liang; J. Y. Shiao; J. F. Lin; M. C. Su; C. H. Hsin; F. J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Determination of Particulate-Bound Formaldehyde from Burning Incense by Solid Phase Microextraction - S. W. Liou; C. Y. Chen; T. T. Yang; J. M. Lin (Bulletin of Environmental Contamination and Toxicology, 2008)

Expression and immunogenic comparison of VP2 and VP3 from marine birnavirus - H‐J Xu; J‐G Lin; C‐X Zhang; S Suzuki (Journal of Fish Diseases, 2008)
The coding regions for the major epitopes of structural protein VP2 ( vp2e ) and structural protein VP3 were amplified from marine birnavirus (MABV) cDNA and efficiently expressed as glutathione S‐transferase (GST) fusion proteins in Escherichia coli . Polyclonal antibodies against VP2e and VP3 were raised in rabbits and fish using the purified proteins of GST/VP2e and GST/VP3. The rabbit anti‐serum against VP3 was more sensitive than the rabbit anti‐VP2e serum in detecting virus in MABV‐infected fish, while fish anti‐VP2e serum showed a stronger neutralization response than fish anti‐VP3 serum.

Using FANP approach on selection of competitive priorities based on cleaner production implementation: a case study in PCB manufacturer, Taiwan - M. L. Tseng; Y. H. Lin; A. S. F. Chiu; J. C. H. Liao (Clean Technologies and Environmental Policy, 2008)

Dissipation of Pendimethalin in the Garlic (Allium sativum L.) under Subtropical Condition - H. T. Lin; S. W. Chen; C. J. Shen; C. Chu (Bulletin of Environmental Contamination and Toxicology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Image processing of FORMOSAT‐2 data for monitoring the South Asia tsunami - C.‐C. Liu; J.‐G. Liu; C.‐W. Lin; A.‐M. Wu; S.‐H. Liu; C.‐L. Shieh (International Journal of Remote Sensing, 2007)

Ganoderma lucidum polysaccharide peptide reduced the production of proinflammatory cytokines in activated rheumatoid synovial fibroblast - Y. W. Ho; J. S. L. Yeung; P. K. Y. Chiu; W. M. Tang; Z. B. Lin; R. Y. K. Man; C. S. Lau (Molecular and Cellular Biochemistry, 2007)

Characteristics of Carbonaceous Aerosol at Taichung Harbor, Taiwan during Summer and Autumn Period of 2005 - Guor-Cheng Fang; S. C. Lee; Wen-Jhy Lee; Yan Cheng; I-Cherng Lin (Environmental Monitoring and Assessment, 2007)

Arsenic Distribution in a Tilapia (Oreochromis mossambicus) Water-Sediment Aquacultural Ecosystem in Blackfoot Disease Hyperendemic Areas - S. -W. Wang; K. -H. Lin; Y. -M. Hsueh; C. -W. Liu (Bulletin of Environmental Contamination and Toxicology, 2007)

Volatile Organic Compound Exposure of Suburban Elementary Students in Taiwan - C.-Y. Peng; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2007)

Volatile Organic Compound Exposure of Suburban Elementary Students in Taiwan - C.-Y. Peng; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2007)

A numerical study of the influence of urban expansion on monthly climate in dry autumn over the Pearl River Delta, China - W. S. Lin; C.-H. Sui; L. M. Yang; X. M. Wang; R. R. Deng; S. J. Fan; C. S. Wu; A. Y. Wang; S. K. Fong; H. Lin (Theoretical and Applied Climatology, 2007)

Apoptosis-dependent and -independent mechanisms mediate the phagocytic recognition/clearance of the HL60-A1 transfectants with prolonged survival - C.-L. Chou; L.-L. Chiang; C.-T. Yu; H.-C. Chen; K.-Y. Lee; S.-M. Lin; C.-D. Huang; W.-T. Liu; P.-C. Chou; C.-H. Wang; H.-C. Lin; H.-P. Kuo; et al. (Inflammation Research, 2007)

Mitochondrial DNA phylogeography of Glyptothorax fokiensis and Glyptothorax hainanensis in Asia - X.‐L. Chen; T.‐Y. Chiang; H.‐D. Lin; H.‐S. Zheng; K.‐T. Shao; Q. Zhang; K.‐C. Hsu (Journal of Fish Biology, 2007)
Whole mitochondrial DNA cytochrome b sequences in 62 fish from 13 locations in Southeast China identified two major clades corresponding to two allopatric taxa, Glyptothorax fokiensis fokiensis and Glyptothorax fokiensis hainanensis . Reciprocal monophyly and a molecular clock separation between these two taxa of 2·3 million years indicate these taxa should be elevated to species. Mismatch distributions and Fu’s F S statistic suggest that both G. fokiensis and G. hainanensis have experienced recent population expansions. Analysis of molecular variance indicates that most of the genetic variation resides among populations within both species, with Φ ST = 0·645 for G. fokiensis and 0·801 for G. hainanensis , suggesting restricted gene flow among populations. Significant correlations between the geographic and the genetic distances provide support for the importance of geographic isolations between populations. Nested clade analysis also confirms low levels of genetic exchanges between the two major groups and between populations within each group. The phylogeographical pattern among populations of Glyptothorax in East Asia can be attributed to historical fragmentations, demographic expansions and occasional long‐distance dispersals stimulated by tectonic activity and Ice Age climate changes.

The contents and forms of solid-phase species of radioactive strontium and cesium in Taiwan soils - S. W. Chang Chien; M. C. Wang; C. L. Chiu; Yu-Ming Lin; Shu-Ying Lai (Environmental Monitoring and Assessment, 2007)

Numerical comparison study of cloud microphysical parameterization schemes for a moderate snowfall event in North China - W. S. Lin; C.-H. Sui; C. Bueh; A. Wang; S. Fan; C. Wu; S. Fong; J. Li; J. Meng (Meteorology and Atmospheric Physics, 2007)

Serum Heat Shock Protein (HSP70) and Its Antibody (Anti-HSP70) Levels in Male Foundry Workers in Taiwan - C.-J. Chen; H.-J. Wen; S.-H. Liu; M.-S. Lin; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2006)

Tissue Accumulation of Arsenic Compounds in Aquacultural and Wild Mullet (Mugil cephalus) - C.-W. Liu; K.-H. Lin; C.-S. Jang (Bulletin of Environmental Contamination and Toxicology, 2006)

Albino inflorescence proliferation of Dendrocalamus latiflorus - C. S. Lin; M. C. Tseng; P. I. Hong; W. C. Chang (In Vitro Cellular & Developmental Biology - Plant, 2006)

Identification of elongation factor 1α as a potential associated binding partner for Akt2 - Janet Lau; Laura A. Castelli; Emme C. K. Lin; S. Lance Macaulay (Molecular and Cellular Biochemistry, 2006)

Climatic Change, Wars and Dynastic Cycles in China Over the Last Millennium - David D. Zhang; C. Y. Jim; George C-S Lin; Yuan-Qing He; James J. Wang; Harry F. Lee (Climatic Change, 2006)

Enhanced viability of a nervous necrosis virus‐infected stable cell line over‐expressing a fusion product of the zfBcl‐x L and green fluorescent protein genes - S‐P Chen; H‐L Yang; H‐Y Lin; M‐C Chen; J‐L Wu; J‐R Hong (Journal of Fish Diseases, 2006)
Nervous necrosis virus (NNV) infection induces host cell apoptosis by an ill‐understood process. We utilized a fusion between enhanced green fluorescent protein (EGFP) and the zfBcl‐x L gene in GL‐av cells to select for zfBcl‐x L stable cell lines and to assess the effectiveness of the anti‐apoptotic protein Bcl‐x L in circumventing NNV‐induced cell death. Stable EGFP and EGFP‐Bcl‐x L ‐expressing clones were obtained at high purity within 2.5–3 months. In the latter, the EGFP‐Bcl‐x L fusion protein (approximately 58.2 kDa, as ascertained by Western blot) was predominantly targeted to mitochondria. We assayed for apoptosis in red‐spotted grouper NNV Tainan no. 1 (RGNNV TN1)‐infected cells with terminal deoxynucleotidyl transferase (TdT)‐mediated end labelling (TUNEL) of DNA at different virus doses. NNV infection of NNV Bcl‐x L GL‐av cell line revealed a protective effect, with a decrease in TUNEL‐positive cells of 7%, 8% and 31.8% at 24, 48 and 72 h, respectively. In addition, RGNNV infection of the Bcl‐x L GL‐av cell line revealed a protective effect, with an enhanced viability of 3%, 40% and 73% at 24, 48, and 72 h, respectively. We conclude that NNV‐induced apoptotic cell death can be lessened in transgenic grouper fish cells.

Seismo-Geochemical Variations in SW Taiwan: Multi-Parameter Automatic Gas Monitoring Results - T. F. Yang; C.-C. Fu; V. Walia; C.-H. Chen; L. L. Chyi; T.-K. Liu; S.-R. Song; M. Lee; C.-W. Lin; C.-C. Lin (Pure and Applied Geophysics, 2006)

Use of a fluorescent membrane probe to identify zooxanthellae in hospite among dissociated endoderm cell culture from coral - C.-S. Chen; H.-P. Lin; C.-C. Yeh; L.-S. Fang (Protoplasma, 2005)

Potential Exposure to VOCs Caused by Dry Process Photocopiers: Results From a Chamber Study - D.-J. Hsu; H.-L. Huang; C.-H. Chien; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2005)

Industrial wideband noise reduction for hearing aids using a headset with adaptive-feedback active noise cancellation - J. -H. Lin; P. -C. Li; S. -T. Tang; P. -T. Liu; S. -T. Young (Medical & Biological Engineering & Computing, 2005)

Characterisation of the welsh onion isolate of Shallot yellow stripe virus from China - J. Chen; C.-B. Wei; H.-Y. Zheng; Y.-H. Shi; M. J. Adams; L. Lin; Q.-Y. Zhang; S.-J. Wang; J.-P. Chen (Archives of Virology, 2005)

Adaptive filtering of evoked potentials using higher-order adaptive signal enhancer with genetic-type variable step-size prefilter - B. -S. Lin; B. -S. Lin; F. -C. Chong; F. Lai (Medical & Biological Engineering & Computing, 2005)

Isolation and characterization of actinomycetes antagonistic to pathogenic Vibrio spp. from nearshore marine sediments - J. L. You; L. X. Cao; G. F. Liu; S. N. Zhou; H. M. Tan; Y. C. Lin (World Journal of Microbiology and Biotechnology, 2005)

Mining the structural knowledge of high-dimensional medical data using isomap - S. Weng; C. Zhang; Z. Lin; X. Zhang (Medical & Biological Engineering & Computing, 2005)

Thallium in Whole Blood Samples from College Students in Taiwan - T.-S. Lin; C.-L. Chang (Bulletin of Environmental Contamination and Toxicology, 2005)

Phylogenetic analysis of classical swine fever virus in Taiwan - C. H. Pan; M. H. Jong; T. S. Huang; H. F. Liu; S. Y. Lin; S. S. Lai (Archives of Virology, 2005)

Trace Elements in Cultured Tilapia (Oreochromis mossambicus): Results from a Farm in Southern Taiwan - T.-S. Lin; C.-S. Lin; C.-L. Chang (Bulletin of Environmental Contamination and Toxicology, 2005)

Mapping QTL associated with resistance to Fusarium head blight in the Nanda2419נWangshuibai population. I. TypeII resistance - F. Lin; Z. X. Kong; H. L. Zhu; S. L. Xue; J. Z. Wu; D. G. Tian; J. B. Wei; C. Q. Zhang; Z. Q. Ma (Theoretical and Applied Genetics, 2004)

Whole Blood Vanadium in Taiwanese College Students - T.-S. Lin; C.-L. Chang; F.-M. Shen (Bulletin of Environmental Contamination and Toxicology, 2004)

Acute Aquatic Toxicity of N-Methyl-2-Pyrrolidinone to Daphnia magna - C.-H. Lan; C.-Y. Peng; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2004)

Natural frequency assessment of stability of root keeper magnetic devices - H. -M. Huang; D. -Z. Liu; Y. -Y. Shiau; C. -Y. Yeh; C. -T. Lin; S. -Y. Lee (Medical & Biological Engineering & Computing, 2004)

Adaptive processing bandwidth adjustment for laser Doppler flowmetry - Y. Y. Chen; Y. H. Lin; I. C. Jan; R. S. Liu; N. K. Chou; G. -J. Jan (Medical & Biological Engineering & Computing, 2004)

Excavating Y-chromosome haplotype strata in Anatolia - Cengiz Cinnioglu; Roy King; Toomas Kivisild; Ersi Kalfoglu; Sevil Atasoy; Gianpiero L. Cavalleri; Anita S. Lillie; Charles C. Roseman; Alice A. Lin; Kristina Prince; Peter J. Oefner; Peidong Shen; et al. (Human Genetics, 2004)

Application of a ?Big-Tree? model to regional climate modeling: a sensitivity study - X.-M. Zeng; M. Zhao; R.-C. Yu; N.-S. Lin; Y.-Q. Zheng; L.-J. Zhang; R.-J. Zhang (Theoretical and Applied Climatology, 2003)

Surfactant proteinA and B genetic variants predispose to idiopathic pulmonary fibrosis - Moises Selman; Hung-Mo Lin; Martha Montao; Audrey L. Jenkins; Andrea Estrada; Zhenwu Lin; Guirong Wang; Susan L. DiAngelo; Xiaoxuan Guo; Todd M. Umstead; C. Max Lang; Annie Pardo; et al. (Human Genetics, 2003)

Historical biogeography and phylogenetic relationships of the genus Chamaecyparis (Cupressaceae) inferred from chloroplast DNA polymorphism - W. P. Wang; C. Y. Hwang; T. P. Lin; S. Y. Hwang (Plant Systematics and Evolution, 2003)

Prospective study of serum retinol, β-carotene, β-cryptoxanthin, and lutein/zeaxanthin and esophageal and gastric cancers in China - Christian C. Abnet; You-Lin Qiao; Sanford M. Dawsey; Dennis W. Buckman; Chung S. Yang; William J. Blot; Zhi-Wei Dong; Philip R. Taylor; Steven D. Mark (Cancer Causes & Control, 2003)

General Toxicity Prediction Approach for Mixtures Containing Polar Narcotic Chemicals - Z. Lin; C. Wu; P. Shi; L. Wang; S. Gao (Bulletin of Environmental Contamination and Toxicology, 2003)

Detection ofBurkholderia pseudomallei in rice fields with PCR-based technique - C. M. Kao; S. C. Chen; Y. S. Chen; H. M. Lin; Y. L. Chen (Folia Microbiologica, 2003)

A method for inflorescence proliferation - C.-S. Lin; C.-T. Chen; C.-C. Lin; W.-C. Chang (Plant Cell Reports, 2003)

Dissecting the pet18mutation in Saccharomyces cervisiae: HTL1encodes a 7-kDa polypeptide that interacts with components of the RSC complex - Y.-M. Lu; Y.-R. Lin; A. Tsai; Y.-S. Hsao; C.-c. Li; M. Y. Cheng (Molecular Genetics and Genomics, 2003)

Involvement of the terminus of grouper betanodavirus capsid protein in virus-like particle assembly - M. W. Lu; C. S. Lin (Archives of Virology, 2003)

Establishment of cell lines from a tropical grouper, Epinephelus awoara (Temminck & Schlegel), and their susceptibility to grouper irido‐ and nodaviruses - Y‐S Lai; J A C John; C‐H Lin; I‐C Guo; S‐C Chen; K Fang; C‐H Lin; C‐Y Chang (Journal of Fish Diseases, 2003)
Four tropical marine fish cell lines have been established from the eye, fin, heart and swim bladder of grouper, Epinephelus awoara (Temminck & Schlegel). Optimum media and temperature conditions for maximum growth were standardized. The eye and swim bladder cells were mostly epithelial, but the fin and heart cells were mostly fibroblastic. The viability of cells was 95% after 1 year of storage in liquid nitrogen (−196 °C). Besides these four cell lines, previously established grouper brain, kidney and liver cell lines were also used for a viral susceptibility study which showed that all the cell lines were sensitive to grouper iridovirus, whereas only brain, fin and liver cell lines were susceptible to the yellow grouper nervous necrosis virus (a nodavirus). Electron microscopy studies of the grouper irido‐ and nodaviruses in ultrathin sections of infected cells showed an abundance of viral particles in the cytoplasm of the virus‐infected cells indicating the effective replication of these two viruses. It is suggested that these cell lines can be used for the isolation of putative fish specific viruses and provide a valuable tool to study the mechanisms of host–pathogen interactions. Furthermore, these cell lines upon transfection, using pEGFP‐C1 and pEGFP‐aMT 2.5 (ayu metallothionein promoter), produced significant fluorescent signals indicating their utility for exogenous studies.

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

Residential Water Supply as a Likely Cause of Community-Acquired Legionnaires' Disease in an Immunocompromised Host - Chen Y-S.; Lin W-R.; Liu Y-C.; Chang C-L.; Gan V-L.; Huang W-K.; Huang T-S.; Wann S-R.; Lin H-H.; Lee S.; Huang C-K.; Chin C.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

A genetic linkage map of Nicotiana plumbaginifolia/ Nicotiana longiflora based on RFLP and RAPD markers - T. Y. Lin; Y. Y. Kao; S. Lin; R. F. Lin; C. M. Chen; C. H. Huang; C. K. Wang; Y. Z. Lin; C. C. Chen (Theoretical and Applied Genetics, 2001)

Sphingolipids as biomarkers of fumonisin exposure and risk of esophageal squamous cell carcinoma in China - Christian C. Abnet; Craig B. Borkowf; You-Lin Qiao; Paul S. Albert; Elaine Wang; Alfred H. Merrill; Steven D. Mark; Zhi-Wei Dong; Philip R. Taylor; Sanford M. Dawsey (Cancer Causes & Control, 2001)

Rapid molecular analysis of the haemagglutinin gene of human influenza A H3N2 viruses isolated in Spain from 1996 to 2000 - M. T. Coiras; J. C. Aguilar; M. Galiano; S. Carlos; V. Gregory; Y. P. Lin; A. Hay; P. Pérez-Breña (Archives of Virology, 2001)

RS-100642-198, a novel sodium channel blocker, provides differential neuroprotection against hypoxia/hypoglycemia, veratridine or glutamate-mediated neurotoxicity in primary cultures of rat cerebellar neurons - Jitendra R. Dave; Yu Lin; Haresh S. Ved; Michael L. Koenig; Larry Clapp; John Hunter; Frank C. Tortella (Neurotoxicity Research, 2001)

Bioaccumulation of Arsenic in Aquacultural Large-Scale Mullet Liza macrolepis from Blackfoot Disease Area in Taiwan - M.-C. Lin; C.-M. Liao; C.-W. Liu; S. Singh (Bulletin of Environmental Contamination and Toxicology, 2001)

Propagation of yellow grouper nervous necrosis virus (YGNNV) in a new nodavirus‐susceptible cell line from yellow grouper, Epinephelus awoara (Temminck & Schlegel), brain tissue - Y‐S Lai; S Murali; H‐C Chiu; H‐Y Ju; Y‐S Lin; S‐C Chen; I‐C Guo; K Fang; C‐Y Chang (Journal of Fish Diseases, 2001)
A nodavirus was isolated from diseased yellow grouper, Epinephelus awoara , larvae cultured in southern Taiwan. The histopathology and RT–PCR results confirmed that it was a fish nodavirus; its coat protein gene sequence was similar to that of red spotted grouper nervous necrosis virus (RGNNV) and it is named yellow grouper nervous necrosis virus (YGNNV). A new nodavirus‐susceptible cell line, grouper brain (GB) was established and characterized from the brain tissue of yellow grouper. The GB cells multiplied well in Leibovitz’s L‐15 medium supplemented with 10% foetal bovine serum at temperatures between 24 and 32 °C, and have been subcultured more than 80 times, becoming a continuous cell line. The GB cell line consists of fibroblast‐like cells and some epithelioid cells. The cell line yielded titres of YGNNV up to 10 8.5 TCID 50 mL –1 . The GB cells effectively replicated the virus at 28 °C, which could be purified to homogeneity by caesium chloride gradient centrifugation. Electron microscopy studies showed that purified virus particles were 25–30 nm in diameter. The cytoplasm of infected cells was filled with aggregates of virus particles. These results indicate that the GB cell line is a significant tool for the study of fish nodaviruses.

Molecular epidemiology of enterovirus 71 in Taiwan - P.-Y. Chu; K.-H. Lin; K.-P. Hwang; L.-C. Chou; C.-F. Wang; S.-R. Shih; J.-R. Wang; Y. Shimada; H. Ishiko (Archives of Virology, 2001)

Blood and Urine Cadmium Levels in Relation to Demographic and Life Style in Middle Aged and Elderly Men - Y. C. Chen; Y. S. Pu; R. S. Lin; C. Y. Yang; M. K. Lai; S. H. Liu; F.-C. Sung (Bulletin of Environmental Contamination and Toxicology, 2001)

Characterization of grouper nervous necrosis virus (GNNV) - S C Chi; B J Lo; S C Lin (Journal of Fish Diseases, 2001)
Grouper nervous necrosis virus (GNNV) was isolated from moribund grouper larvae, Epinephelus sp., using a fish cell line GF‐1. The present study describes the biochemical and biophysical properties of GNNV and the expression of GNNV in diseased grouper larvae. Viral protein was detectable in most of the GNNV‐infected GF‐1 cells by the fluorescent antibody technique (FAT) after 12 h post‐infection (p.i.), although no cytopathic effect (CPE) appeared at that time. Clear CPE developed on the third day, and complete disintegration of the monolayer occurred over the subsequent two days. The infectivity of GNNV can be blocked following treatment at 60 °C for 1 h. GNNV was sensitive to pH 3 and pH 10–12 with a 4 log 10 drop in infectivity. Purified GNNV was analysed by SDS–PAGE, and then stained with periodic acid silver. The positive staining indicated that its two capsid proteins were glycoproteins. Genomic RNAs of GNNV were extracted from purified virions and analysed. The molecular weights of genomic RNAs were 1.02 × 10 6 and 0.50 × 10 6 Da. The T2 region of the coat protein gene of GNNV was amplified by polymerase chain reaction (PCR), and the multiple alignment of the T2 sequence of two GNNV isolates with four genotypes of fish nodaviruses revealed that these two isolates (GNNV9410 and GNNV9508) belong to the red‐spotted grouper nervous necrosis virus (RGNNV) genotype. The tissue distribution of GNNV in naturally infected grouper larvae was investigated by in situ hybridization using a dig‐labelled probe, which showed that GNNV was not only detected in the brain and retina, but also in the gill, skeletal muscle, liver, pyloric gland, intestine and blood cells in the heart.

Differences in size and growth rates of male and female migrating Japanese eels in Pearl River, China - W. N. Tzeng; H. R. Lin; C. H. Wang; S. N. Xu (Journal of Fish Biology, 2000)
The Sr/Ca ratios in otoliths of silver Japanese eels Anguilla japonica , in Pearl River, China, indicated that both sexes did not stay in brackish water and grew in fresh water from the glass eel stage until spawning migration. This did not support the hypothesis that females tended to distribute upstream and males might be restricted to estuaries. The back‐calculated total length of males at glass eel stage was not significantly different from that of females, indicating that the hypothesis that small glass eels became males and larger ones became females may not be true. The mean (±S.D.) age and total length of males at migration were 6·4±1·6 years and 48·3±4·5 cm, which were significantly smaller than for females, 8·3±1·6 years and 61·4±4·1 cm. The age of migration was related inversely to growth rate for both sexes. Growth parameters of the von Bertalanffy growth equation were K =0·21 cm year°1, L ∞ =55·7 cm and t o =‐0·55 year for males and K =0·14 cm year −1 , L ∞ =77·5 cm and t o =‐0·60 year for females. The difference in asymptotic length ( L ∞ ) between males and females may be because females postpone migration to achieve larger size for maximizing reproductive success.

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)

Development of a plant regeneration system based on friable embryogenic callus in the ornamental Alstroemeria - H. -S. Lin; C. van der Toorn; K. J. J. M. Raemakers; R. G. F. Visser; M.J. De Jeu; E. Jacobsen (Plant Cell Reports, 2000)

Flavonoids as inducers of extracellular proteins and exopolysaccharides of Sinorhizobium fredii - C. C. Lin; Y. C. Chen; S. C. Song; L. P. Lin (Biology and Fertility of Soils, 1999)

Compression studies of gibbsite and its high-pressure polymorph - E. Huang; J.-F. Lin; J. Xu; T. Huang; Y.-C. Jean; H.-S. Sheu (Physics and Chemistry of Minerals, 1999)

Cadmium-Inducible Metallothionein in Tilapia ( Oreochromis mossambicus ) - S. M. Wu *, , C. F. Weng; M. J. Yu; C. C. Lin; S. T. Chen; J. C. Hwang; P. P. Hwang (Bulletin of Environmental Contamination and Toxicology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Δ 9 -THC training dose as a determinant for ( R )-methanandamide generalization in rats - T. U. C. Järbe; R. J. Lamb; A. Makriyannis; S. Lin; A. Goutopoulos (Psychopharmacology, 1998)

A morphological study of cells isolated from the perfused gill of dab and Atlantic salmon - S.‐H. Lin; G. A. Davidson; C. J. Secombes; A. E. Ellis (Journal of Fish Biology, 1998)
Single cell suspensions were derived from the gills of dab Limanda limanda and Atlantic salmon Salmo salar which were free from blood cell contamination. Gills were perfused with heparinized saline before the cells were liberated from their resident position using a procedure employing chelating agents and collagenase digestion. Cells were characterized using light and electron microscopy as well as histochemical staining. The results indicate that the cell types resident in the gill tissue should be capable of expressing local immune competence. Small and large lymphocytes, macrophages, neutrophils, eosinophilic granule cells, goblet cells, chloride cells and cells of unusual morphology were identified especially the presence of goblet cells apparently within epithelial‐like cells.

Micropropagation of Bambusa edulis through nodal explants of field-grown culms and flowering of regenerated plantlets - C.-S. Lin; W.-C. Chang (Plant Cell Reports, 1998)

Effects of zinc supplementation on the plasma glucose level and insulin activity in genetically obese (ob/ob) mice - Ming-Der Chen; Shy-Jane Liou; Pi-Yao Lin; Vivian C. Yang; Paul S. Alexander; Wen-Han Lin (Biological Trace Element Research, 1998)

Transgenic peppermint ( Mentha × piperita L.) plants obtained by cocultivation with Agrobacterium tumefaciens - X. Niu; K. Lin; P. M. Hasegawa; R. A. Bressan; S. C. Weller (Plant Cell Reports, 1998)

Estimation of myocardial glucose utilisation with PET using the left ventricular time-activity curve as a non-invasive input function - X. Li; D. Feng; K. -P. Lin; S. -C. Huang (Medical & Biological Engineering & Computing, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Three-dimensional P-wave Velocity Structure of the Bear Valley Region of Central California - C.-H. Lin; S. W. Roecker (Pure and Applied Geophysics, 1997)

Regulation of lipoprotein metabolism by estrogen in inbred strains of mice occurs primarily by posttranscriptional mechanisms - Rai Ajit K. Srivastava; Elaine S. Krul; Renee C. Lin; Gustav Schonfeld (Molecular and Cellular Biochemistry, 1997)

Stimulation of testicular function by exogenous testosterone in male protandrous black porgy, Acanthopagrus schlegeli - E.‐L. Lau; B.‐Y. Lin; F.‐Y. Lee; L.‐T. Sun; S. Dufour; C.‐F. Chang (Journal of Fish Biology, 1997)
When 4 mg of testosterone (T) per kg food was given to 1‐year‐old protandrous male black porgy Acanthopagrus schlegeli for 7 months, gonadosomatic index was significantly higher than when the dose was 0.5 mg kg −1 food. Both doses of T prolonged the spawning season, and increased the number of spermiating fish and milt volume. Sperm concentrations were similar in spermiating black porgy from the treated and control groups. Low levels of oestradiol‐17β were observed during the experimental period while elevated levels of plasma T were observed only in March in both control and T‐treated groups. Significantly higher levels of plasma 11‐ketotestosterone (11‐KT) were observed in the 0.5‐ and 4.0‐mg T‐treated groups during the spawning season as compared to the control group. The present data suggest that both 0.5‐ and 4·0‐mg T doses stimulate testicular weight, increase numbers of spermiating males and milt volume without affecting the sperm concentrations. Plasma 11‐KT concentrations were elevated during T treatment and closely correlated with testicular development and spermiation.

Sweet potato (Ipomoea batatas) trypsin inhibitors expressed in transgenic tobacco plants confer resistance against Spodoptera litura - K.-W. Yeh; M.-I. Lin; S.-J. Tuan; Y.-M. Chen; C.-J. Lin; S.-S. Kao (Plant Cell Reports, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

A preliminary study of the formation of precipitation systems under undisturbed conditions during TAMEX - C. -S. Chen; C. -Y. Lin (Meteorology and Atmospheric Physics, 1997)

A high resolution numerical study of Gulf of Mexico fronts and eddies - D. E. Dietrich; C. A. Lin; A. Mestas-Nunez; D. S. Ko (Meteorology and Atmospheric Physics, 1997)

Determination of urinary zinc, chromium, and copper in steel production workers - C. J. Horng; S. R. Lin (Biological Trace Element Research, 1996)

Capsid protein of cucumber mosaic virus accumulates in the nuclei and at the periphery of the nucleoli in infected cells - N. -S. Lin; C. -E. Hsieh; Y. -H. Hsu (Archives of Virology, 1996)

Envelope gene sequences of human T-lymphotropic virus type I in Taiwan - M. T. Lin; Y. C. Chen; P. J. Chen; Y. C. Yang; J. L. Tang; J. M. Wu; S. E. Chuang; C. S. Yang (Archives of Virology, 1996)

N-Nitroso-N-(3-keto-1,2-butanediol)-3′-nitrotyramine - C. -J. Wang; H. -P. Huang; T. -H. Tseng; Y. -L. Lin; S. -J. Shiow (Archives of Toxicology, 1995)

Different sensitivities to cadmium in tilapia larvae (Oreochromis mossambicus; teleostei) - P. P. Hwang; S. W. Lin; H. C. Lin (Archives of Environmental Contamination and Toxicology, 1995)

A long lytic cycle in filamentous phage Cf1tv infectingXanthomonas campestris pv.citri - T. -T. Kuo; C. -C. Chiang; S. -Y. Chen; J. -H. Lin; J. -L. Kuo (Archives of Virology, 1994)

Simultaneous determination of Zn, Cd, Pb, and Cu in urine of patients with blackfoot disease using anodic stripping voltammetry - T. C. Pan; C. J. Horng; S. R. Lin; T. H. Lin; C. W. Huang (Biological Trace Element Research, 1993)

The skin, tongue, and brain as favorable organs for hog cholera diagnosis by immunofluorescence - I. C. Pan; T. S. Huang; C. H. Pan; Shenq-Yi Chern; Shu-Hwae Lee; Y. L. Lin; B. Y. Huang; C. C. Lin; N. J. Li; J. P. Lin; Y. H. Yang; S. Y. Chiu; et al. (Archives of Virology, 1993)

Evolutionary study on the coxsackievirus A 24 variant causing acute hemorrhagic conjunctivitis by oligonucleotide mapping analysis of RNA genome - K. Miyamura; N. Takeda; M. Tanimura; T. Ogino; S. Yamazaki; C. -W. Chen; K. -H. Lin; S. Y. Lin; A. Ghafoor; M. Yin-Murphy (Archives of Virology, 1990)